Blend containing rPET and copolyester, and preparation method and product thereof

By using a blend of high content of PET and copolyester in polyester materials and adopting a shear heating mixing process, the problem of difficulty in taking into account transparency and recyclability is solved, and efficient and environmentally friendly polyester material preparation is achieved .

CN119432023APending Publication Date: 2025-02-14SHANGHAI ZHIHUIJU MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411811060.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-11-19
Filing Date
2024-12-10
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art is difficult to develop a transparent, easy to recycle and high PET content polyester material, especially when preparing thick wall products, transparency and recyclability are difficult to take into account.

Method used

Using a blend containing PET and copolyester, a high PET with a mixture is prepared by adding sterically hindered monomer diol residues to the copolyester and mixing molten PET and copolyester through shear heating mixing equipment. Blend of content, good transparency and easy recycling.

Benefits of technology

The transparency and ease of recycling of high content PET is achieved, the haze is reduced when preparing thick-walled products, the commercial needs are met, and the carbon emissions are significantly reduced when regenerated PET is used.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The embodiment of the invention relates to a blend containing PET and copolyester, a preparation method and a product thereof, the blend comprises 20-50 wt% of a first copolyester, more than 50 wt% and less than 80 wt% of PET and optionally more than 0 wt% and less than 20 wt% of a compatilizer, the first copolyester comprises a dicarboxylic acid component and a diol component, the dicarboxylic acid component comprises terephthalic acid residues in a specific content range, and the diol component comprises sterically hindered monomer diol residues, ethylene glycol residues and diethylene glycol residues in a specific content range; the article is a renewable transparent article comprising the blend described above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polyester, and in particular relates to a blend containing rPET and copolyester, a preparation method and a product thereof. Background Art

[0002] Polyethylene terephthalate (PET) is widely used in commerce to make various products. Such products are easy to recycle and regenerate. After regeneration, recycled PET (rPET) is obtained for recycling. PET can be recycled by physical methods or chemical methods. The physical method is to obtain physical rPET by crushing, cleaning, drying and other physical methods of recycled PET after consumption, and then recycle it; the chemical method is to depolymerize PET at high temperature to obtain small molecular monomers or oligomers, and then purify these monomers and use them again to make PET. The PET regenerated by this method is called chemical rPET. In comparison, the physical regeneration process is simpler, can reduce carbon emissions on a large scale, and is more energy-saving and environmentally friendly.

[0003] Commercially, there is a large demand for transparent and easily recyclable polyester materials to make various products needed in people's lives. However, transparency and easy recycling are contradictory requirements: transparent materials are mostly non-crystalline or weakly crystalline polyesters, such as PETG (polyethylene terephthalate-1,4-cyclohexanedimethanol ester), which has no obvious melting point and a low softening point. It is easy to stick when heated during the recycling process, which increases the difficulty of recycling and has poor recyclability; while crystalline polyester materials, such as PET (polyethylene terephthalate), are easy to recycle and have good recyclability, but are easy to crystallize. This easy crystallization property can be cooled and formed before crystallization when preparing thin-walled containers (such as the pure water packaging bottles commonly seen in life), so the transparency is better, but when made into thick-walled products, the haze is high and the transparency is poor.

[0004] When a non-crystalline or weakly crystalline polyester (such as PETG) is mixed with a relatively low-content crystalline polyester (such as virgin PET or recycled PET) to form a blend, the technical problem of transparency and easy recycling when preparing thick-walled products can be partially solved, making the products both transparent and easy to recycle. However, this solution cannot use high-content PET as a raw material. Thick-walled products mixed with high-content PET raw materials have high haze and poor transparency, which is difficult to meet commercial needs. In particular, when recycled PET is used as a raw material in order to obtain the technical effect of carbon reduction and environmental protection, the use of a relatively low-content rPET will obviously not produce satisfactory carbon reduction and environmental protection effects.

[0005] The prior art urgently needs a new material that is transparent, easy to recycle and contains a high content of PET, a preparation method thereof and a product thereof. Summary of the invention

[0006] In order to solve the above technical problems, the embodiments of the present invention provide a blend containing PET and copolyester, a preparation method thereof and a product thereof.

[0007] According to the first aspect of the present invention, an embodiment of the present invention provides a blend containing PET and copolyester.

[0008] <1> A blend containing PET and copolyester, the blend comprising:

[0009] (1) 20-50 wt% of a first copolyester, wherein the first copolyester has an undetectable crystallization temperature Tc or a crystallization enthalpy ΔHc of less than 1 J / g as measured by differential scanning calorimetry at a cooling rate of 10° C. / min;

[0010] The first copolyester comprises a dicarboxylic acid component and a diol component;

[0011] The dicarboxylic acid component comprises:

[0012] a) 90-100 mol % of terephthalic acid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the first copolyester;

[0013] b) 0-10 mol % of other aliphatic and / or aromatic diacid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the first copolyester;

[0014] The diol component comprises:

[0015] a) based on the total molar amount of diol residues in the first copolyester being 100%, greater than 50 mol% and less than 100 mol% of sterically hindered diol residues, wherein in the first copolyester, the sterically hindered diol residues include:

[0016] 0-100 mol % neopentyl glycol residues;

[0017] 0-30 mol % of 2-methyl-1,3-propanediol residues;

[0018] 0-50 mol % of 1,4-cyclohexanedimethanol residues;

[0019] b) 0-50 mol % of ethylene glycol residues, based on 100 mol % of the total molar amount of glycol residues in the first copolyester;

[0020] c) 0-15 mol % of diethylene glycol residues, based on 100 mol % of the total molar amount of diol residues in the first copolyester;

[0021] (2) greater than 50% by weight and less than 80% by weight of PET;

[0022] (3) greater than 0 wt % and less than 20 wt % of a compatibilizer;

[0023] The blend has a measurable crystallization temperature Tc or a crystallization enthalpy ΔHc greater than 1 J / g as measured by differential scanning calorimetry at a cooling rate of 10°C / min;

[0024] When the blend is used to prepare a sheet with a thickness of 4 mm by an injection molding process, the haze of the sheet is less than 50%;

[0025] Based on the total molar amount of diol residues in the blend as 100%, the content of the diol residues of the sterically hindered monomer is greater than 15 mol%.

[0026] <2> like <1> In the blend, the compatibilizer is the second copolyester.

[0027] <3> like <2> In the blend, the compatibilizer is a second copolyester containing a sterically hindered monomer.

[0028] <4> like <3> The blend, wherein the second copolyester comprises a dicarboxylic acid component and a diol component;

[0029] The dicarboxylic acid component of the second copolyester comprises:

[0030] a) 90 to 100 mole % of terephthalic acid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the second copolyester;

[0031] b) 0-10 mol % of other aliphatic and / or aromatic diacid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the second copolyester;

[0032] The diol component in the second copolyester comprises:

[0033] a) based on the total molar amount of diol residues in the second copolyester being 100%, 10-50 mol% of diol residues of a sterically hindered monomer, wherein the sterically hindered monomer is a diol;

[0034] b) 50-90 mol % of ethylene glycol residues, based on 100 mol % of the total molar amount of glycol residues in the second copolyester;

[0035] c) 0-15 mol % of diethylene glycol residues, based on 100 mol % of the total molar amount of diol residues in the second copolyester.

[0036] <5> like <3> or <4> In the blend, the steric hindered monomer in the second copolyester is one or more of neopentyl glycol, 2-methyl-1,3-propanediol, and 1,4-cyclohexanedimethanol.

[0037] According to the second aspect of the present invention, an embodiment of the present invention provides a blend containing PET and copolyester.

[0038] <6> A blend containing PET and copolyester, the blend comprising:

[0039] (1) 20-50 wt% of a first copolyester, wherein the first copolyester has an undetectable crystallization temperature Tc or a crystallization enthalpy ΔHc of less than 1 J / g as measured by differential scanning calorimetry at a cooling rate of 10° C. / min;

[0040] The first copolyester comprises a dicarboxylic acid component and a diol component;

[0041] The dicarboxylic acid component comprises:

[0042] a) 90-100 mol % of terephthalic acid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the first copolyester;

[0043] b) 0-10 mol % of other aliphatic and / or aromatic diacid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the first copolyester;

[0044] The diol component comprises:

[0045] a) based on the total molar amount of diol residues in the first copolyester being 100%, greater than 50 mol% and less than 100 mol% of sterically hindered diol residues, wherein in the first copolyester, the sterically hindered diol residues include:

[0046] 0-100 mol % neopentyl glycol residues;

[0047] 0-30 mol % of 2-methyl-1,3-propanediol residues;

[0048] 0-50 mol % of 1,4-cyclohexanedimethanol residues;

[0049] b) 0-50 mol % of ethylene glycol residues, based on 100 mol % of the total molar amount of glycol residues in the first copolyester;

[0050] c) 0-15 mol % of diethylene glycol residues, based on 100 mol % of the total molar amount of diol residues in the first copolyester;

[0051] (2) greater than 50% by weight and less than 80% by weight of PET;

[0052] The first copolyester and the PET are mixed and melted by a shear heating mixing device;

[0053] The blend has a measurable crystallization temperature Tc or a crystallization enthalpy ΔHc greater than 1 J / g as measured by differential scanning calorimetry at a heating rate of 10°C / min;

[0054] When the blend is used to prepare a sheet with a thickness of 4 mm by an injection molding process, the haze of the sheet is less than 50%;

[0055] Based on the total molar amount of diol residues in the blend as 100%, the content of the diol residues of the sterically hindered monomer is greater than 15 mol%.

[0056] <7> like <1> or <6> The blend, based on the total weight of the blend being 100%, has a content of the steric hindered monomer greater than 15 weight percent.

[0057] <8> like <1> or <6> In the blend, the steric hindered monomer in the first copolyester includes neopentyl glycol.

[0058] <9> like <8> The blend, based on the total molar amount of glycol residues in the first copolyester being 100%, has a neopentyl glycol residue content of 55-90 mol %.

[0059] <10> like <9> In the blend, based on the total molar amount of glycol residues in the first copolyester being 100%, the content of neopentyl glycol residues is 60-80 mol%.

[0060] <11> like <10> The blend, based on the total molar amount of glycol residues in the first copolyester being 100%, has a neopentyl glycol residue content of 65-70 mol %.

[0061] <12> like <1> or <6> In the blend, the steric hindered monomers in the first copolyester include neopentyl glycol and 2-methyl-1,3-propanediol.

[0062] <13> like <12> In the blend, based on the total molar amount of glycol residues in the first copolyester being 100%, the content of neopentyl glycol residues is 40-90 mol%, and the content of 2-methyl-1,3-propanediol residues is 5-25 mol%.

[0063] <14> like <13> In the blend, based on the total molar amount of glycol residues in the first copolyester being 100%, the content of neopentyl glycol residues is 45-80 mol %, and the content of 2-methyl-1,3-propanediol residues is 5-15 mol %.

[0064] <15> like <14> In the blend, based on the total molar amount of glycol residues in the first copolyester being 100%, the content of neopentyl glycol residues is 50-70 mol %, and the content of 2-methyl-1,3-propanediol residues is 5-10 mol %.

[0065] <16> like <1> or <6> In the blend, the steric hindered monomers in the first copolyester include neopentyl glycol and 1,4-cyclohexanedimethanol.

[0066] <17> like <16> In the blend, based on the total molar amount of glycol residues in the first copolyester being 100%, the content of neopentyl glycol residues is 10-90 mol%, and the content of 1,4-cyclohexanedimethanol residues is 10-45 mol%.

[0067] <18> like <17> In the blend, based on the total molar amount of glycol residues in the first copolyester being 100%, the content of neopentyl glycol residues is 20-70 mol %, and the content of 1,4-cyclohexanedimethanol residues is 20-40 mol %.

[0068] <19> like <18> In the blend, based on the total molar amount of glycol residues in the first copolyester being 100%, the content of neopentyl glycol residues is 25-60 mol %, and the content of 1,4-cyclohexanedimethanol residues is 25-40 mol %.

[0069] <20> like <19> In the blend, based on the total molar amount of glycol residues in the first copolyester being 100%, the content of neopentyl glycol residues is 25-45 mol%, and the content of 1,4-cyclohexanedimethanol residues is 20-35 mol%.

[0070] <21> like <1> or <6> In the blend, the steric hindered monomer in the first copolyester includes neopentyl glycol, 1,4-cyclohexanedimethanol and 2-methyl-1,3-propanediol.

[0071] <22> like <21> The blend, based on the total molar amount of glycol residues in the first copolyester as 100%, has a neopentyl glycol residue content of 10-90 mol%, a 1,4-cyclohexanedimethanol residue content of 10-45 mol%, and a 2-methyl-1,3-propanediol residue content of 5-25 mol%.

[0072] <23> like <22> The blend, based on the total molar amount of glycol residues in the first copolyester as 100%, has a neopentyl glycol residue content of 20-70 mol%, a 1,4-cyclohexanedimethanol residue content of 15-40 mol%, and a 2-methyl-1,3-propanediol residue content of 5-15 mol%.

[0073] <24> like <23> The blend, based on the total molar amount of glycol residues in the first copolyester as 100%, has a neopentyl glycol residue content of 25-60 mol%, a 1,4-cyclohexanedimethanol residue content of 20-40 mol%, and a 2-methyl-1,3-propanediol residue content of 5-10 mol%.

[0074] <25> like <1> or <6> In the blend, the glass transition temperature Tg of the first copolyester measured by differential scanning calorimetry at a heating rate of 10°C / min is greater than 60°C and less than 100°C.

[0075] <26> like <1> or <6> The blend has an intrinsic viscosity of 0.50 to 1.2 dL / g when measured in 60 / 40 (wt / wt) phenol / tetrachloroethane at a concentration of 0.5 g / 100 ml at 25°C.

[0076] <27> like <1> or <6> In the blend, the PET is rPET.

[0077] <28> like <1> or <6> The blend, the PET is: virgin PET, or physical rPET, or chemical rPET, or a mixture of virgin PET and physical rPET, or a mixture of virgin PET and chemical rPET, or a mixture of physical rPET and chemical rPET, or a mixture of virgin PET, physical rPET and chemical rPET.

[0078] <29> like <1> or <6> The blend has a melting temperature greater than 220°C.

[0079] According to the third aspect of the present invention, an embodiment of the present invention provides a method for preparing a blend containing PET and copolyester.

[0080] <30> A method for preparing a blend containing PET and copolyester comprises the following steps:

[0081] (1) mixing and melting 20-50 wt % of the first copolyester and more than 50 wt % and less than 80 wt % of PET by a shear heating mixing device to obtain a melt blend;

[0082] The first copolyester has an undetectable crystallization temperature Tc or a crystallization enthalpy ΔHc of less than 1 J / g as measured by differential scanning calorimetry at a cooling rate of 10° C. / min;

[0083] The first copolyester comprises a dicarboxylic acid component and a diol component;

[0084] The dicarboxylic acid component comprises:

[0085] a) 90-100 mol % of terephthalic acid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the first copolyester;

[0086] b) 0-10 mol % of other aliphatic and / or aromatic diacid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the first copolyester;

[0087] The diol component comprises:

[0088] a) based on the total molar amount of diol residues in the first copolyester being 100%, greater than 50 mol% and less than 100 mol% of sterically hindered diol residues, wherein in the first copolyester, the sterically hindered diol residues include:

[0089] 0-100 mol % neopentyl glycol residues;

[0090] 0-30 mol % of 2-methyl-1,3-propanediol residues;

[0091] 0-50 mol % of 1,4-cyclohexanedimethanol residues;

[0092] b) 0-50 mol % of ethylene glycol residues, based on 100 mol % of the total molar amount of glycol residues in the first copolyester;

[0093] c) 0-15 mol % of diethylene glycol residues, based on 100 mol % of the total molar amount of diol residues in the first copolyester;

[0094] (2) cooling the molten blend to form a shape;

[0095] The blend has a measurable crystallization temperature Tc or a crystallization enthalpy ΔHc greater than 1 J / g as measured by differential scanning calorimetry at a heating rate of 10°C / min;

[0096] When the blend is used to prepare a sheet with a thickness of 4 mm by an injection molding process, the haze of the sheet is less than 50%;

[0097] Based on the total molar amount of diol residues in the blend as 100%, the content of the diol residues of the sterically hindered monomer is greater than 15 mol%.

[0098] <31> like <30> In the preparation method, the shearing, heating and mixing equipment is a twin-screw extruder or a reactor with a stirring device.

[0099] <32> like <30> In the preparation method, based on the total weight of the blend being 100%, the content of the steric hindrance monomer is greater than 15% by weight.

[0100] <33> like <30> In the preparation method, the steric hindered monomer in the first copolyester includes neopentyl glycol.

[0101] <34> like <33> In the preparation method, based on the total molar amount of glycol residues in the first copolyester being 100%, the content of the neopentyl glycol residues is 55-90 mol%.

[0102] <35> like <34> In the preparation method, based on the total molar amount of glycol residues in the first copolyester being 100%, the content of the neopentyl glycol residues is 60-80 mol%.

[0103] <36> like <35> In the preparation method, based on the total molar amount of glycol residues in the first copolyester being 100%, the content of the neopentyl glycol residues is 65-70 mol%.

[0104] <37> like <30> In the preparation method, the steric hindered monomers in the first copolyester include neopentyl glycol and 2-methyl-1,3-propanediol.

[0105] <38> like <37> In the preparation method, based on the total molar amount of glycol residues in the first copolyester being 100%, the content of neopentyl glycol residues is 40-90 mol%, and the content of 2-methyl-1,3-propanediol residues is 5-25 mol%.

[0106] <39> like <38> In the preparation method, based on the total molar amount of glycol residues in the first copolyester being 100%, the content of neopentyl glycol residues is 45-80 mol%, and the content of 2-methyl-1,3-propanediol residues is 5-15 mol%.

[0107] <40> like <39> In the preparation method, based on the total molar amount of glycol residues in the first copolyester being 100%, the content of neopentyl glycol residues is 50-70 mol%, and the content of 2-methyl-1,3-propanediol residues is 5-10 mol%.

[0108] <41> like <30> In the preparation method, the steric hindered monomers in the first copolyester include neopentyl glycol and 1,4-cyclohexanedimethanol.

[0109] <42> like <41> In the preparation method, based on the total molar amount of glycol residues in the first copolyester being 100%, the content of neopentyl glycol residues is 10-90 mol%, and the content of 1,4-cyclohexanedimethanol residues is 10-45 mol%.

[0110] <43> like <42> In the preparation method, based on the total molar amount of glycol residues in the first copolyester being 100%, the content of neopentyl glycol residues is 20-70 mol%, and the content of 1,4-cyclohexanedimethanol residues is 20-40 mol%.

[0111] <44> like <43> In the preparation method, based on the total molar amount of glycol residues in the first copolyester being 100%, the content of neopentyl glycol residues is 25-60 mol%, and the content of 1,4-cyclohexanedimethanol residues is 25-40 mol%.

[0112] <45> like <44> In the preparation method, based on the total molar amount of glycol residues in the first copolyester being 100%, the content of neopentyl glycol residues is 25-45 mol%, and the content of 1,4-cyclohexanedimethanol residues is 20-35 mol%.

[0113] <46> like <30> In the preparation method, the steric hindered monomers in the first copolyester include neopentyl glycol, 1,4-cyclohexanedimethanol and 2-methyl-1,3-propanediol.

[0114] <47> like <46> In the preparation method, based on the total molar amount of glycol residues in the first copolyester being 100%, the content of neopentyl glycol residues is 10-90 mol%, the content of 1,4-cyclohexanedimethanol residues is 10-45 mol%, and the content of 2-methyl-1,3-propanediol residues is 5-25 mol%.

[0115] <48> like <47> In the preparation method, based on the total molar amount of glycol residues in the first copolyester being 100%, the content of neopentyl glycol residues is 20-70 mol%, the content of 1,4-cyclohexanedimethanol residues is 15-40 mol%, and the content of 2-methyl-1,3-propanediol residues is 5-15 mol%.

[0116] <49> like <48> In the preparation method, based on the total molar amount of glycol residues in the first copolyester being 100%, the content of neopentyl glycol residues is 25-60 mol%, the content of 1,4-cyclohexanedimethanol residues is 20-40 mol%, and the content of 2-methyl-1,3-propanediol residues is 5-10 mol%.

[0117] <50> like <30> In the preparation method, the glass transition temperature Tg of the first copolyester is greater than 60°C and less than 100°C.

[0118] <51> like <30> The preparation method has an intrinsic viscosity of 0.50 to 1.2 dL / g of the blend measured in 60 / 40 (wt / wt) phenol / tetrachloroethane at a concentration of 0.5 g / 100 ml at 25°C.

[0119] <52> like <30> In the preparation method, the PET is rPET.

[0120] <53> like <30> In the preparation method, the PET is: virgin PET, or physical rPET, or chemical rPET, or a mixture of virgin PET and physical rPET, or a mixture of virgin PET and chemical rPET, or a mixture of physical rPET and chemical rPET, or a mixture of virgin PET, physical rPET and chemical rPET.

[0121] According to a fourth aspect of the present invention, an embodiment of the present invention provides a regenerable transparent product.

[0122] <54> A recyclable transparent product, the product comprising <1> to <29> A blend of one of <30> to <53> The blend prepared by the preparation method described in one of the above.

[0123] <55> A renewable transparent article comprising a blend of PET and a copolyester, the blend comprising:

[0124] (1) 20-50 wt% of a first copolyester, wherein the first copolyester has an undetectable crystallization temperature Tc or a crystallization enthalpy ΔHc of less than 1 J / g as measured by differential scanning calorimetry at a cooling rate of 10° C. / min;

[0125] The first copolyester comprises a dicarboxylic acid component and a diol component;

[0126] The dicarboxylic acid component comprises:

[0127] a) 90-100 mol % of terephthalic acid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the first copolyester;

[0128] b) 0-10 mol % of other aliphatic and / or aromatic diacid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the first copolyester;

[0129] The diol component comprises:

[0130] a) based on the total molar amount of diol residues in the first copolyester being 100%, greater than 50 mol% and less than 100 mol% of sterically hindered diol residues, wherein in the first copolyester, the sterically hindered diol residues include:

[0131] 0-100 mol % neopentyl glycol residues;

[0132] 0-30 mol % of 2-methyl-1,3-propanediol residues;

[0133] 0-50 mol % of 1,4-cyclohexanedimethanol residues;

[0134] b) 0-50 mol % of ethylene glycol residues, based on 100 mol % of the total molar amount of glycol residues in the first copolyester;

[0135] c) 0-15 mol % of diethylene glycol residues, based on 100 mol % of the total molar amount of diol residues in the first copolyester;

[0136] (2) greater than 50% by weight and less than 80% by weight of PET;

[0137] (3) greater than 0 wt % and less than 20 wt % of a compatibilizer;

[0138] The blend has a measurable crystallization temperature Tc or a crystallization enthalpy ΔHc greater than 1 J / g as measured by differential scanning calorimetry at a cooling rate of 10°C / min;

[0139] The content of the sterically hindered monomer diol residue is greater than 15 mol % based on the total molar amount of diol residues in the blend as 100%;

[0140] The haze of the product is below 50%.

[0141] <56> like <55> In the product, the compatibilizer is the second copolyester.

[0142] <57> like <56> In the product, the compatibilizer is a second copolyester containing a sterically hindered monomer.

[0143] <58> like <57> The article, wherein the second copolyester comprises a dicarboxylic acid component and a diol component;

[0144] The dicarboxylic acid component of the second copolyester comprises:

[0145] a) 90 to 100 mole % of terephthalic acid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the second copolyester;

[0146] b) 0-10 mol % of other aliphatic and / or aromatic diacid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the second copolyester;

[0147] The diol component in the second copolyester comprises:

[0148] a) based on the total molar amount of diol residues in the second copolyester being 100%, 10-50 mol% of diol residues of a sterically hindered monomer, wherein the sterically hindered monomer is a diol;

[0149] b) 50-90 mol % of ethylene glycol residues, based on 100 mol % of the total molar amount of glycol residues in the second copolyester;

[0150] c) 0-15 mol % of diethylene glycol residues, based on 100 mol % of the total molar amount of diol residues in the second copolyester.

[0151] <59> like <57> or <58> In the product, the steric hindered monomer in the second copolyester is one or more of neopentyl glycol, 2-methyl-1,3-propanediol, and 1,4-cyclohexanedimethanol.

[0152] <60> A renewable transparent article comprising a blend of PET and a copolyester, the blend comprising:

[0153] (1) 20-50 wt% of a first copolyester, wherein the first copolyester has an undetectable crystallization temperature Tc or a crystallization enthalpy ΔHc of less than 1 J / g as measured by differential scanning calorimetry at a cooling rate of 10° C. / min;

[0154] The first copolyester comprises a dicarboxylic acid component and a diol component;

[0155] The dicarboxylic acid component comprises:

[0156] a) 90-100 mol % of terephthalic acid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the first copolyester;

[0157] b) 0-10 mol % of other aliphatic and / or aromatic diacid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the first copolyester;

[0158] The diol component comprises:

[0159] a) based on the total molar amount of diol residues in the first copolyester being 100%, greater than 50 mol% and less than 100 mol% of sterically hindered diol residues, wherein in the first copolyester, the sterically hindered diol residues include:

[0160] 0-100 mol % neopentyl glycol residues;

[0161] 0-30 mol % of 2-methyl-1,3-propanediol residues;

[0162] 0-50 mol % of 1,4-cyclohexanedimethanol residues;

[0163] b) 0-50 mol % of ethylene glycol residues, based on 100 mol % of the total molar amount of glycol residues in the first copolyester;

[0164] c) 0-15 mol % of diethylene glycol residues, based on 100 mol % of the total molar amount of diol residues in the first copolyester;

[0165] (2) greater than 50% by weight and less than 80% by weight of PET;

[0166] The first copolyester and the PET are mixed and melted by a shear heating mixing device;

[0167] The blend has a measurable crystallization temperature Tc or a crystallization enthalpy ΔHc greater than 1 J / g as measured by differential scanning calorimetry at a heating rate of 10°C / min;

[0168] The content of the sterically hindered monomer diol residue is greater than 15 mol % based on the total molar amount of diol residues in the blend as 100%;

[0169] The haze of the product is below 50%.

[0170] <61> A renewable transparent product comprises a blend containing PET and copolyester, wherein the blend is prepared by the following preparation method, which comprises the following steps:

[0171] (1) mixing and melting 20-50 wt % of the first copolyester and more than 50 wt % and less than 80 wt % of PET by a shear heating mixing device to obtain a melt blend;

[0172] The first copolyester has an undetectable crystallization temperature Tc or a crystallization enthalpy ΔHc of less than 1 J / g as measured by differential scanning calorimetry at a cooling rate of 10° C. / min;

[0173] The first copolyester comprises a dicarboxylic acid component and a diol component;

[0174] The dicarboxylic acid component comprises:

[0175] a) 90-100 mol % of terephthalic acid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the first copolyester;

[0176] b) 0-10 mol % of other aliphatic and / or aromatic diacid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the first copolyester;

[0177] The diol component comprises:

[0178] a) based on the total molar amount of diol residues in the first copolyester being 100%, greater than 50 mol% and less than 100 mol% of sterically hindered diol residues, wherein in the first copolyester, the sterically hindered diol residues include:

[0179] 0-100 mol % neopentyl glycol residues;

[0180] 0-30 mol % of 2-methyl-1,3-propanediol residues;

[0181] 0-50 mol % of 1,4-cyclohexanedimethanol residues;

[0182] b) 0-50 mol % of ethylene glycol residues, based on 100 mol % of the total molar amount of glycol residues in the first copolyester;

[0183] c) 0-15 mol % of diethylene glycol residues, based on 100 mol % of the total molar amount of diol residues in the first copolyester;

[0184] (2) cooling the molten blend to form a shape;

[0185] The blend has a measurable crystallization temperature Tc or a crystallization enthalpy ΔHc greater than 1 J / g as measured by differential scanning calorimetry at a heating rate of 10°C / min;

[0186] The content of the sterically hindered monomer diol residue is greater than 15 mol % based on the total molar amount of diol residues in the blend as 100%;

[0187] The haze of the product is below 50%.

[0188] <62> like <61> The product, the shearing, heating and mixing equipment is a twin-screw extruder or a reactor with a stirring device.

[0189] <63> like <55> or <60> or <61> In the product, based on the total weight of the blend being 100%, the content of the steric hindered monomer is greater than 15% by weight.

[0190] <64> like <55> or <60> or <61> In the product, the steric hindered monomer in the first copolyester includes neopentyl glycol.

[0191] <65> like <64> The product, based on the total molar amount of glycol residues in the first copolyester being 100%, has a neopentyl glycol residue content of 55-90 mol%.

[0192] <66> like <65> The product, based on the total molar amount of glycol residues in the first copolyester being 100%, has a neopentyl glycol residue content of 60-80 mol%.

[0193] <67> like <66> The product, based on the total molar amount of glycol residues in the first copolyester being 100%, has a neopentyl glycol residue content of 65-70 mol%.

[0194] <68> like <55> or <60> or <61> In the product, the steric hindered monomers in the first copolyester include neopentyl glycol and 2-methyl-1,3-propanediol.

[0195] <69> like <68> The product, based on the total molar amount of glycol residues in the first copolyester being 100%, has a neopentyl glycol residue content of 40-90 mol% and a 2-methyl-1,3-propanediol residue content of 5-25 mol%.

[0196] <70> like <69> In the product, based on the total molar amount of glycol residues in the first copolyester being 100%, the content of neopentyl glycol residues is 45-80 mol%, and the content of 2-methyl-1,3-propanediol residues is 5-15 mol%.

[0197] <71> like <70> The product, based on the total molar amount of glycol residues in the first copolyester being 100%, has a neopentyl glycol residue content of 50-70 mol% and a 2-methyl-1,3-propanediol residue content of 5-10 mol%.

[0198] <72> like <55> or <60> or <61> In the product, the steric hindered monomers in the first copolyester include neopentyl glycol and 1,4-cyclohexanedimethanol.

[0199] <73> like <72> The product, based on the total molar amount of glycol residues in the first copolyester being 100%, has a neopentyl glycol residue content of 10-90 mol% and a 1,4-cyclohexanedimethanol residue content of 10-45 mol%.

[0200] <74> like <73> The product, based on the total molar amount of glycol residues in the first copolyester being 100%, has a neopentyl glycol residue content of 20-70 mol% and a 1,4-cyclohexanedimethanol residue content of 20-40 mol%.

[0201] <75> like <74> The product, based on the total molar amount of glycol residues in the first copolyester being 100%, has a neopentyl glycol residue content of 25-60 mol% and a 1,4-cyclohexanedimethanol residue content of 25-40 mol%.

[0202] <76> like <75> The product, based on the total molar amount of glycol residues in the first copolyester being 100%, has a neopentyl glycol residue content of 25-45 mol% and a 1,4-cyclohexanedimethanol residue content of 20-35 mol%.

[0203] <77> like <55> or <60> or <61> In the product, the steric hindered monomers in the first copolyester include neopentyl glycol, 1,4-cyclohexanedimethanol and 2-methyl-1,3-propanediol.

[0204] <78> like <77> The product, based on the total molar amount of glycol residues in the first copolyester as 100%, has a neopentyl glycol residue content of 10-90 mol%, a 1,4-cyclohexanedimethanol residue content of 10-45 mol%, and a 2-methyl-1,3-propanediol residue content of 5-25 mol%.

[0205] <79> like <78> The product, based on the total molar amount of glycol residues in the first copolyester as 100%, has a neopentyl glycol residue content of 20-70 mol%, a 1,4-cyclohexanedimethanol residue content of 15-40 mol%, and a 2-methyl-1,3-propanediol residue content of 5-15 mol%.

[0206] <80> like <79> The product, based on the total molar amount of glycol residues in the first copolyester as 100%, has a neopentyl glycol residue content of 25-60 mol%, a 1,4-cyclohexanedimethanol residue content of 20-40 mol%, and a 2-methyl-1,3-propanediol residue content of 5-10 mol%.

[0207] <81> like <55> or <60> or <61> The product, the first copolyester has a glass transition temperature Tg greater than 60°C and less than 100°C as measured by differential scanning calorimetry at a heating rate of 10°C / min.

[0208] <82> like <55> or <60> or <61> The product has an intrinsic viscosity of 0.50 to 1.2 dL / g when measured in 60 / 40 (wt / wt) phenol / tetrachloroethane at a concentration of 0.5 g / 100 ml at 25°C.

[0209] <83> like <55> or <60> or <61> In the product, the PET is rPET.

[0210] <84> like <55> or <60> or <61> The product described herein, wherein the PET is: virgin PET, or physical rPET, or chemical rPET, or a mixture of virgin PET and physical rPET, or a mixture of virgin PET and chemical rPET, or a mixture of physical rPET and chemical rPET, or a mixture of virgin PET, physical rPET and chemical rPET.

[0211] <85> like <54> or <55> or <60> or <61> The product has a thickness of 0.04-10 mm.

[0212] <86> like <85> The product has a thickness of 0.2-10 mm.

[0213] <87> like <86> The product has a thickness of 4-10 mm.

[0214] <88> like <54> or <55> or <60> or <61> The product has a melting temperature greater than 220°C.

[0215] Beneficial effects of the embodiments of the present invention:

[0216] In an embodiment of the present invention, a first copolyester containing steric hindered monomer diol residues, PET and a compatibilizer are mixed to form a blend, or the first copolyester containing steric hindered monomer diol residues and PET are mixed using a shear heating process to form a blend, thereby providing a novel blend, which comprises: 20-50 weight % of the first copolyester, greater than 50 weight % and less than 80 weight % of PET, and optionally greater than 0 weight % and less than 20 weight % of the compatibilizer; based on the total molar amount of diol residues in the first copolyester as 100%, the content of steric hindered monomer diol residues greater than 50 mole % and less than 100 mole %, based on the total molar amount of diol residues in the blend as 100%, and the content of steric hindered monomer diol residues greater than 15 mole %.

[0217] The blend and the product made from the blend have low haze, good transparency, are easy to recycle (have certain crystallinity and a melting temperature greater than 220° C.), and have a high PET content. In particular, when PET is physical rPET, the blend can reduce carbon emissions on a large scale relative to chemical rPET and virgin polyester materials. According to the data of the US APR in 2020 (see Virgin vs. Recycled Plastic Life Cycle Assessment Energy Profile and Life Cycle Assessment Environmental Burdens), the carbon dioxide emissions of virgin PET are 2.23 kg CO2 / kg, and the carbon dioxide emissions of physical rPET are 0.91 kg CO2 / kg. When more than 50% by weight of physical rPET is used, compared with virgin polyester containing the same molar content of hindered monomer diol residues, carbon dioxide emissions can be reduced by more than 29%. DETAILED DESCRIPTION

[0218] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. However, those skilled in the art will appreciate that the present invention is not limited to the following embodiments.

[0219] According to a first aspect of the present invention, an embodiment of the present invention provides a blend containing PET and copolyester, wherein the blend comprises:

[0220] (1) 20-50 wt% of a first copolyester, wherein the first copolyester has an undetectable crystallization temperature Tc or a crystallization enthalpy ΔHc of less than 1 J / g as measured by differential scanning calorimetry at a cooling rate of 10° C. / min;

[0221] (2) greater than 50% by weight and less than 80% by weight of PET;

[0222] (3) A compatibilizer in an amount of more than 0 wt% and not more than 20 wt%.

[0223] According to a second aspect of the present invention, an embodiment of the present invention provides a blend containing PET and copolyester,

[0224] (1) 20-50 wt% of a first copolyester, wherein the first copolyester has an undetectable crystallization temperature Tc or a crystallization enthalpy ΔHc of less than 1 J / g as measured by differential scanning calorimetry at a cooling rate of 10° C. / min;

[0225] (2) greater than 50% by weight and less than 80% by weight of PET;

[0226] The first copolyester and the PET are mixed and melted by a shear heating mixing device.

[0227] Preferably, the temperature of the mixed melting is 250-310°C.

[0228] Preferably, the mixing and melting is performed under a pressure of 10-2000 Pa. By mixing and melting under low pressure, the degradation of the copolyester can be reduced.

[0229] Preferably, after the mixed and melted, the molten blend obtained by the mixed and melted is filtered; preferably, in the filtering step, the molten blend is filtered through a filter screen, and the pore size of the filter screen is less than 100 meshes. By filtering the molten blend, impurities in the blend can be at least partially removed, thereby reducing the haze of the blend and improving the transparency.

[0230] According to a third aspect of the present invention, an embodiment of the present invention provides a method for preparing a blend containing PET and copolyester, comprising the following steps:

[0231] (1) mixing and melting 20-50 wt % of the first copolyester and more than 50 wt % and less than 80 wt % of PET by a shear heating mixing device to obtain a melt blend;

[0232] (2) Cooling the molten blend to form a shape.

[0233] Preferably, the temperature of the mixed melting is 250-310°C.

[0234] Preferably, the mixed melting is carried out under a pressure of 10-2000 Pa.

[0235] Preferably, the method further comprises a filtering step: filtering the molten blend obtained in step (1); preferably, in the filtering step, the molten blend is filtered through a filter; preferably, the pore size of the filter is less than 100 meshes. By filtering, impurities in the blend can be at least partially removed, thereby reducing the haze of the blend and improving transparency.

[0236] According to the first aspect of the present invention, the present invention obtains a transparent, easily recyclable blend with a high PET content by blending a first copolyester, PET and a compatibilizer.

[0237] According to the second and third aspects of the present invention, the present invention can obtain a transparent, easily recyclable blend with a high PET content by mixing and melting the first copolyester and PET using a shear heating mixing device.

[0238] As is known to all, when preparing thin-walled containers, crystalline polyesters (such as PET) can be cooled and formed before crystallization due to the fast cooling and forming speed, so the transparency is better. When manufacturing thick-walled products, due to the large thickness of the product, the surface layer can be cooled and formed before crystallization to maintain transparency, but the inside of the thick wall is difficult to cool quickly, resulting in crystallization of the inside of the wall before cooling and forming, which will produce a product with an opaque interior and a transparent outer layer. Therefore, when manufacturing thick-walled products, transparency and recyclability are two indicators that are difficult to take into account. When non-crystalline or weakly crystalline polyesters (such as PETG) are blended with crystalline polyesters with a lower content (such as virgin PET or recycled PET) to make a blend, the above-mentioned technical problems that are difficult to take into account can only be partially solved when the PET content is low.

[0239] The inventors have found that when the PET content in the blend is high (greater than 50% by weight in the blend), even if the content of non-crystalline or weakly crystalline polyester (such as PETG, PET modified with CHDM) is increased, the obtained blend is still opaque. The reasons for the opacity of the blend include two factors: one is the crystallization of the blend, and the other is the compatibility between different polyesters. The opacity caused by the two factors of crystallization and compatibility is not the same. Crystallization will make the edge of the blend transparent while the internal crystallization is whitish and opaque, while compatibility causes the overall opacity of the blend. The opacity of the blend is often caused by the coexistence of the two factors. Therefore, when solving the technical problem of opacity, it is often necessary to overcome the opacity caused by the two factors at the same time. Overcoming only one of the factors cannot completely solve the technical problem of opacity.

[0240] In order to solve the technical problem of opacity when the PET content in the above blend is high, the inventors found that when the first copolyester and PET as described in the embodiment of the present invention are mixed with the component content of the present invention, by adding a compatibilizer or by using a shear heating mixing process, the prepared blend and the product made of the blend have a certain crystallinity and are easy to recycle, and can simultaneously overcome the opacity caused by the two factors of crystallization and incompatibility, so as to have good transparency, and the PET content is high. The blend comprises: 20-50% by weight of the first copolyester, more than 50% by weight and less than 80% by weight of PET, and optionally more than 0% by weight and less than 20% by weight of the compatibilizer; based on the total molar amount of diol residues in the first copolyester as 100%, the content of the steric hindered monomer diol residues greater than 50% by mole and less than 100% by mole, based on the total molar amount of diol residues in the blend as 100%, the content of the steric hindered monomer diol residues is greater than 15% by mole. In addition, the addition of the compatibilizer and the use of the shear heating mixing process can further improve the transparency of the blend and its products. On the contrary, when preparing a blend of PET and the first copolyester in the content described in the embodiment of the present invention, if no compatibilizer is used and no shear heating mixing process is adopted, the prepared blend and its product are opaque.

[0241] In the first, second and third aspects of the present invention described above:

[0242] The first copolyester has a crystallization temperature T of 10°C / min measured by differential scanning calorimetry. c Unable to detect or crystallize enthalpy ΔH c Less than 1 J / g;

[0243] The first copolyester comprises a dicarboxylic acid component and a diol component;

[0244] The dicarboxylic acid component comprises:

[0245] a) 90-100 mol % of terephthalic acid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the first copolyester;

[0246] b) 0-10 mol % of other aliphatic and / or aromatic diacid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the first copolyester;

[0247] The diol component comprises:

[0248] a) based on the total molar amount of diol residues in the first copolyester being 100%, greater than 50 mol% and less than 100 mol% of sterically hindered diol residues, wherein in the first copolyester, the sterically hindered diol residues include:

[0249] 0-100 mol % neopentyl glycol residues;

[0250] 0-30 mol % of 2-methyl-1,3-propanediol residues;

[0251] 0-50 mol % of 1,4-cyclohexanedimethanol residues;

[0252] That is, the steric hindered monomer is selected from one or more of neopentyl glycol, 2-methyl-1,3-propanediol, and 1,4-cyclohexanedimethanol, and its content is within the above numerical range based on the total molar amount of glycol residues in the first copolyester as 100%;

[0253] b) 0-50 mol % of ethylene glycol residues, based on 100 mol % of the total molar amount of glycol residues in the first copolyester;

[0254] c) 0-15 mol % of diethylene glycol residues, based on 100 mol % of the total molar amount of diol residues in the first copolyester;

[0255] The crystallization temperature T of the blend was measured by differential scanning calorimetry at a heating rate of 10°C / min. c Measurable or crystallization enthalpy ΔH c Greater than 1 J / g;

[0256] When the blend is used to prepare a sheet with a thickness of 4 mm using an injection molding process, the haze of the sheet is below 50%; preferably, the haze of the sheet is below 45%; more preferably, the haze of the sheet is below 40%; more preferably, the haze of the sheet is below 35%; more preferably, the haze of the sheet is below 30%; more preferably, the haze of the sheet is below 25%; more preferably, the haze of the sheet is below 20%; more preferably, the haze of the sheet is below 15%.

[0257] Taking the total molar amount of diol residues in the blend as 100%, the content of the diol residues of the sterically hindered monomer is greater than 15 mol%. The content of the diol residues of the sterically hindered monomer in the blend is detected by nuclear magnetic resonance, which is a common technical means in the art and need not be elaborated. It should be noted that when a sterically hindered monomer is used as the diol component of the compatibilizer, the content of the diol residues of the sterically hindered monomer as the diol component of the compatibilizer is included, that is, the sum of the contents of the diol residues of the sterically hindered monomer in the first copolyester and the diol residues of the sterically hindered monomer in the compatibilizer is greater than 15 mol%.

[0258] When the PET in the embodiment of the present invention adopts rPET, there is no special limitation on the rPET. The physical rPET and chemical rPET widely used in the prior art are both included in the scope of the present invention. For example, in one embodiment, the physical rPET may be slightly modified, such as modified with up to 5 mol% of isophthalic acid and / or up to 5 mol% of CHDM or other diols; in one embodiment, the physical rPET may be recycled industrial PET and / or post-consumer PET, for example, post-consumer PET from beverage bottles, or from waste PET fibers and waste PET films.

[0259] In the embodiment of the present invention, the content of PET in the blend is greater than 50 wt % and less than 80 wt %; preferably 55-75 wt %; more preferably 55-70 wt %; more preferably 60-65 wt %.

[0260] In the embodiment of the present invention, the content of the first copolyester in the blend is 20-50 weight %, preferably 25-45 weight %, and more preferably 30-40 weight %.

[0261] The first copolyester of the embodiment of the present invention comprises a dicarboxylic acid component and a diol component.

[0262] The dicarboxylic acid component in the first copolyester comprises:

[0263] a) 90-100 mol % of terephthalic acid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the first copolyester;

[0264] b) 0-10 mol % of other aliphatic and / or aromatic diacid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the first copolyester.

[0265] In the present invention, the molar percentage of terephthalic acid residues is calculated based on the total molar number of dicarboxylic acid residues in the first copolyester as 100%. The first copolyester containing 90 mole % or more of terephthalic acid residues, that is, when the total mole number of dicarboxylic acid residues in the first copolyester is 100 moles, the mole number of terephthalic acid residues is 90 moles or more.

[0266] The "other aliphatic and / or aromatic diacid residues" refers to aliphatic diacid residues and / or aromatic diacid residues other than terephthalic acid residues.

[0267] In one embodiment, the content of terephthalic acid residues in the first copolyester is 90-100 mol %, preferably 95-100 mol %, more preferably 97 mol %, and more preferably 100 mol %.

[0268] In one embodiment, the dicarboxylic acid component comprises an aliphatic dicarboxylic acid, such as cyclohexanedicarboxylic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid and / or dodecanedicarboxylic acid, and the copolyester can be modified using an aliphatic dicarboxylic acid. The aliphatic dicarboxylic acid residue content is 0-10 mol %, preferably 0-8 mol %, more preferably 0-5 mol %, more preferably 0-2 mol %.

[0269] In one embodiment, the dicarboxylic acid component comprises an aromatic dicarboxylic acid, such as phthalic acid or isophthalic acid, and the copolyester can be modified using the aromatic dicarboxylic acid. The diacid residue content of the aromatic dicarboxylic acid is 0-10 mol %, preferably 0.01-10 mol %, more preferably 0.1-10 mol %, more preferably 1-10 mol %, and more preferably 2-9 mol %.

[0270] In one embodiment, the dicarboxylic acid component comprises aliphatic dicarboxylic acids and aromatic dicarboxylic acids, and the total content of aliphatic dicarboxylic acids and aromatic dicarboxylic acids is 0-10 mol %, preferably 0.01-10 mol %, more preferably 0.1-10 mol %, more preferably 1-10 mol %, more preferably 2-9 mol %.

[0271] The diol component in the first copolyester comprises:

[0272] a) based on the total molar amount of diol residues in the first copolyester being 100%, greater than 50 mol% and less than 100 mol% of sterically hindered diol residues, wherein in the first copolyester, the sterically hindered diol residues include:

[0273] 0-100 mol % neopentyl glycol residues;

[0274] 0-30 mol % of 2-methyl-1,3-propanediol residues;

[0275] 0-50 mol % of 1,4-cyclohexanedimethanol residues;

[0276] That is, the steric hindered monomer is selected from one or more of neopentyl glycol, 2-methyl-1,3-propanediol, and 1,4-cyclohexanedimethanol, and its content is within the above numerical range based on the total molar amount of glycol residues in the first copolyester as 100%;

[0277] b) 0-50 mol % of ethylene glycol residues, based on 100 mol % of the total molar amount of glycol residues in the first copolyester;

[0278] c) 0-15 mol % of diethylene glycol residues, based on 100 mol % of the total molar amount of diol residues in the first copolyester.

[0279] In the embodiment of the present invention, for example, the content of diol residues is based on the total molar number of diol residues in the first copolyester as 100%. The first copolyester containing 50 mol% of ethylene glycol residues means that when the total molar number of diol residues in the first copolyester is 100%, the molar percentage of ethylene glycol residues is 50%, that is, when the total molar number of diol residues in the first copolyester is 100 mol, the ethylene glycol residues are 50 mol.

[0280] The sterically hindered monomer is essentially a monomer that can destroy the crystallinity of PET. Such monomers have steric hindrance, thereby destroying the crystallinity of PET.

[0281] In one embodiment, based on the total molar amount of diol residues in the first copolyester as 100%, the content of the diol residues of the sterically hindered monomer is greater than 50 mol % and less than 100 mol %, preferably 60-90 mol %, more preferably 65-80 mol %, more preferably 70-75 mol %.

[0282] In one embodiment, the steric hindered monomer in the first copolyester includes neopentyl glycol; preferably, based on the total molar amount of glycol residues in the first copolyester as 100%, the content of the neopentyl glycol residues is 55-90 mol%, more preferably, based on the total molar amount of glycol residues in the first copolyester as 100%, the content of the neopentyl glycol residues is 60-80 mol%, more preferably, based on the total molar amount of glycol residues in the first copolyester as 100%, the content of the neopentyl glycol residues is 65-70 mol%. The steric hindered monomer in the first copolyester includes neopentyl glycol, which means that the content of neopentyl glycol is not 0.

[0283] In one embodiment, the steric hindered monomer in the first copolyester includes neopentyl glycol and 2-methyl-1,3-propanediol; preferably, based on the total molar amount of the diol residues in the first copolyester as 100%, the content of the neopentyl glycol residues is 40-90 mol%, and the content of the 2-methyl-1,3-propanediol residues is 5-25 mol%; more preferably, based on the total molar amount of the diol residues in the first copolyester as 100%, the content of the neopentyl glycol residues is 45-80 mol%, and the content of the 2-methyl-1,3-propanediol residues is 5-15 mol%; more preferably, based on the total molar amount of the diol residues in the first copolyester as 100%, the content of the neopentyl glycol residues is 50-70 mol%, and the content of the 2-methyl-1,3-propanediol residues is 5-10 mol%. The steric hindered monomer in the first copolyester includes neopentyl glycol and 2-methyl-1,3-propanediol, which means that the content of neopentyl glycol and 2-methyl-1,3-propanediol is not zero.

[0284] In one embodiment, the steric hindered monomer in the first copolyester includes neopentyl glycol and 1,4-cyclohexanedimethanol; preferably, based on the total molar amount of glycol residues in the first copolyester as 100%, the content of the neopentyl glycol residues is 10-90 mol%, and the content of the 1,4-cyclohexanedimethanol residues is 10-45 mol%; more preferably, based on the total molar amount of glycol residues in the first copolyester as 100%, the content of the neopentyl glycol residues is 20-70 mol%, and the content of the 1,4-cyclohexanedimethanol residues is 20-45 mol%. The cyclohexanedimethanol residue content is 20-40 mol%; more preferably, based on the total molar amount of glycol residues in the first copolyester as 100%, the neopentyl glycol residue content is 25-60 mol%, and the 1,4-cyclohexanedimethanol residue content is 25-40 mol%; more preferably, based on the total molar amount of glycol residues in the first copolyester as 100%, the neopentyl glycol residue content is 25-45 mol%, and the 1,4-cyclohexanedimethanol residue content is 20-35 mol%. The steric hindered monomers in the first copolyester include neopentyl glycol and 1,4-cyclohexanedimethanol, which means that the contents of both neopentyl glycol and 1,4-cyclohexanedimethanol are not 0.

[0285] In one embodiment, the steric hindered monomer in the first copolyester includes neopentyl glycol, 1,4-cyclohexanedimethanol and 2-methyl-1,3-propanediol; preferably, based on the total molar amount of glycol residues in the first copolyester as 100%, the content of the neopentyl glycol residues is 10-90 mol%, the content of the 1,4-cyclohexanedimethanol residues is 10-45 mol%, and the content of the 2-methyl-1,3-propanediol residues is 5-25 mol%; more preferably, based on the total molar amount of glycol residues in the first copolyester as 100%, the content of the neopentyl glycol residues is 10-90 mol%, the content of the 1,4-cyclohexanedimethanol residues is 10-45 mol%, and the content of the 2-methyl-1,3-propanediol residues is 5-25 mol%. %, the content of the neopentyl glycol residues is 20-70 mol%, the content of the 1,4-cyclohexanedimethanol residues is 15-40 mol%, and the content of the 2-methyl-1,3-propanediol residues is 5-15 mol%; more preferably, based on the total molar amount of glycol residues in the first copolyester as 100%, the content of the neopentyl glycol residues is 25-60 mol%, the content of the 1,4-cyclohexanedimethanol residues is 20-40 mol%, and the content of the 2-methyl-1,3-propanediol residues is 5-10 mol%. The steric hindered monomer in the first copolyester includes neopentyl glycol, 1,4-cyclohexanedimethanol and 2-methyl-1,3-propanediol means neopentyl glycol, and the contents of 1,4-cyclohexanedimethanol and 2-methyl-1,3-propanediol are not 0.

[0286] In the blend of the embodiment of the present invention, the content of the sterically hindered monomer diol residue is greater than 15 mol %, based on the total molar amount of diol residues in the blend being 100 mol %.

[0287] Preferably, based on 100% of the total weight of the blend, the content of the steric hindered monomer is greater than 15% by weight.

[0288] In one embodiment, the diol component in the first copolyester includes ethylene glycol, and the content of ethylene glycol residues is 0-50 mol% based on the total molar amount of diol residues in the first copolyester as 100%. Preferably, the content of ethylene glycol residues is 5-40 mol%, more preferably, the content of ethylene glycol residues is 10-30 mol%, and more preferably, the content of ethylene glycol residues is 20-25 mol%.

[0289] In one embodiment, the diol component in the first copolyester includes diethylene glycol, and the content of diethylene glycol residues is 0-15 mol%, preferably 5-13 mol%, and more preferably 8-12 mol%, based on the total molar amount of diol residues in the first copolyester. It will be understood by those skilled in the art that some other diol residues may be formed during the processing of polyester, and the diethylene glycol residues described in the embodiments of the present invention include those formed during the processing, or intentionally added, or both.

[0290] In the first, second and third aspects of the present invention:

[0291] The blend or the blend prepared according to the method for preparing the blend may be, for example, slices, or may be particles produced by a granulation device.

[0292] Preferably, the rPET described in the present invention is physical method rPET.

[0293] Preferably, the melting temperature of the blend of the present invention is greater than 220°C.

[0294] Preferably, the blend or the blend prepared according to the preparation method of the blend has an intrinsic viscosity of 0.50 to 1.2 dL / g measured in 60 / 40 (wt / wt) phenol / tetrachloroethane at a concentration of 0.5 g / 100 ml at 25°C.

[0295] Preferably, other additives, such as dyes, flame retardants, reinforcing agents, antistatic agents, antioxidants, etc., may be added to the first copolyester or blend of the present invention so that the blend or the product made thereof has the corresponding expected properties. These additives are commonly used additives in the prior art.

[0296] In addition, the inventors also found that in the blend of the embodiments of the present invention, when the steric hindered monomer in the first copolyester includes 1,4-cyclohexanedimethanol (CHDM), based on the total molar amount of diol residues in the first copolyester as 100%, when the content of 1,4-cyclohexanedimethanol residues is greater than 50 mol%, even if a compatibilizer and / or a shear heating mixing process is used, it is difficult to obtain a transparent blend. Therefore, when the steric hindered monomer in the first copolyester includes 1,4-cyclohexanedimethanol (CHDM), based on the total molar amount of diol residues in the first copolyester as 100%, the content of 1,4-cyclohexanedimethanol residues is below 50 mol%.

[0297] In the embodiment of the present invention, the crystallization temperature Tc of the first copolyester cannot be detected or the crystallization enthalpy ΔH is determined by using differential scanning calorimetry (DSC) according to the measurement method of ASTM D3418 at a cooling rate of 10°C / min. c Less than 1J / g.

[0298] In the embodiment of the present invention, the glass transition temperature T of the first copolyester is measured by differential scanning calorimetry (DSC) with reference to the measurement method of ASTM D3418 at a heating rate of 10° C. / min. g Greater than 60℃ and less than 100℃.

[0299] In a first aspect of the present invention:

[0300] The blend comprises more than 0 wt % and less than 20 wt % of a compatibilizer. Preferably, the blend comprises 5-15 wt % of a compatibilizer; more preferably, the blend comprises 7-10 wt % of a compatibilizer.

[0301] Preferably, the compatibilizer is a second copolyester, which is used to improve the compatibility between the first copolyester and PET. Preferably, the compatibilizer is a second copolyester containing a sterically hindered monomer.

[0302] The compatibility refers to the ability of the various components of the blend to accommodate each other and form a macroscopically uniform material. Mixing two polymer materials with poor compatibility usually results in an opaque material.

[0303] The second copolyester comprises a dicarboxylic acid component and a diol component;

[0304] The dicarboxylic acid component of the second copolyester comprises:

[0305] a) 90 to 100 mole % of terephthalic acid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the second copolyester;

[0306] b) 0-10 mol % of other aliphatic and / or aromatic diacid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the second copolyester;

[0307] The diol component in the second copolyester comprises:

[0308] a) based on the total molar amount of diol residues in the second copolyester being 100%, 10-50 mol% of diol residues of a sterically hindered monomer, wherein the sterically hindered monomer is a diol;

[0309] b) 50-90 mol % of ethylene glycol residues, based on 100 mol % of the total molar amount of glycol residues in the second copolyester;

[0310] c) 0-15 mol % of diethylene glycol residues, based on 100 mol % of the total molar amount of diol residues in the second copolyester.

[0311] The "other aliphatic and / or aromatic diacid residues" refers to aliphatic and / or aromatic diacid residues other than terephthalic acid residues.

[0312] Preferably, the steric hindered monomer in the second copolyester is one or more of neopentyl glycol, 2-methyl-1,3-propanediol, and 1,4-cyclohexanedimethanol.

[0313] The second copolyester is, for example, a mature commercially available copolyester product WS-501 from Jiangyin Huahong, a copolyester product from SK K2012 et al.

[0314] In the first aspect of the present invention, the blend of the first copolyester, PET and the compatibilizer can be prepared by conventional processing techniques known in the art, such as particle physics cold blending, melt mixing after the particles are melted, single-screw extrusion compounding, twin-screw extrusion compounding, batch melt mixing equipment or a combination of the above, and the order in which the three components of the first copolyester, PET and the compatibilizer are mixed is not limited.

[0315] In the second and third aspects of the present invention, the order of heating and mixing the first copolyester and PET is not limited. For example, in one embodiment, the molten mixture is obtained by first shearing and mixing the PET and the first copolyester and then heating and melting them. In another embodiment, the molten mixture is obtained by first heating and melting the PET and the first copolyester separately and then shearing and mixing the two melts. In another embodiment, the molten mixture is obtained by shearing and mixing the PET and the first copolyester while heating.

[0316] The first copolyester in the embodiment of the present invention can be prepared by methods known in the art, for example, the first copolyester can be prepared by esterification of dicarboxylic acid and diol, polycondensation method, or by transesterification of dicarboxylic acid ester and diol monomer, including but not limited to esterification of one or more dicarboxylic acid and one or more diol at a temperature of 200° C. to 315° C., polycondensation at 200-315° C. and a pressure of 0.1 to 760 mmHg to form the first copolyester. In one embodiment, the first copolyester can also be made from recycled monomers recovered by chemical methods.

[0317] The embodiment of the present invention uses differential scanning calorimetry (DSC) to measure the glass transition temperature Tg and melting temperature Tg of the first copolyester and the PET blend at a temperature change rate of 10°C / min according to the measurement method of ASTM D3418. m , crystallization temperature T c , crystallization enthalpy ΔH c The first heating eliminates the thermal history, and then the temperature is lowered to determine the crystallization temperature T c and crystallization enthalpy ΔH c Then raise the temperature and measure T g , melting temperature T m and melting enthalpy ΔH m .

[0318] The haze of the blends of the examples of the present invention was measured and evaluated by the following steps (the comparative examples include an embodiment in which shear heating mixing of a twin-screw extruder is not used, as described below):

[0319] (1) A mixture of the first copolyester, PET and an optional compatibilizer (i.e., containing a compatibilizer or not) is added to a twin-screw extruder, heated to 250-300° C. to melt, and then cooled to form pellets.

[0320] (2) The uniformly mixed particles are injected into a mold by an injection molding machine to prepare a 4 mm thick sheet, the injection molding temperature is 220-280° C., the holding time is 2 seconds, the cooling time is 25 seconds, and the injection time is 2 seconds.

[0321] (3) After the sheet is cooled and formed, the light transmittance and haze of the sheet are tested according to ASTM D1003.

[0322] In the embodiments of the present invention, the intrinsic viscosity IV of the first copolyester and the blend is measured according to the national standard GB / T14190-2008, and the preparation, light transmittance and haze test methods of the first copolyester are the same as those of the above blend.

[0323] In the embodiment of the present invention, an AVANCE-600MHz nuclear magnetic resonance spectrometer was used for testing. About 5 to 10 mg of a dry sample was weighed, dissolved in deuterated trifluoroacetic acid (CF3COOD) solvent, and tested at room temperature.

[0324] According to a fourth aspect of the present invention, an embodiment of the present invention provides a renewable transparent product, wherein the product comprises the blend as described above, or comprises the blend prepared by the preparation method described above.

[0325] The embodiment of the present invention also provides a renewable transparent product, which comprises a blend containing PET and copolyester, wherein the blend comprises:

[0326] (1) 20-50 wt% of a first copolyester, wherein the first copolyester has an undetectable crystallization temperature Tc or a crystallization enthalpy ΔHc of less than 1 J / g as measured by differential scanning calorimetry at a cooling rate of 10° C. / min;

[0327] The first copolyester comprises a dicarboxylic acid component and a diol component;

[0328] The dicarboxylic acid component comprises:

[0329] a) 90-100 mol % of terephthalic acid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the first copolyester;

[0330] b) 0-10 mol % of other aliphatic and / or aromatic diacid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the first copolyester;

[0331] The diol component comprises:

[0332] a) based on the total molar amount of diol residues in the first copolyester being 100%, greater than 50 mol% and less than 100 mol% of sterically hindered diol residues, wherein in the first copolyester, the sterically hindered diol residues include:

[0333] 0-100 mol % neopentyl glycol residues;

[0334] 0-30 mol % of 2-methyl-1,3-propanediol residues;

[0335] 0-50 mol % of 1,4-cyclohexanedimethanol residues;

[0336] b) 0-50 mol % of ethylene glycol residues, based on 100 mol % of the total molar amount of glycol residues in the first copolyester;

[0337] c) 0-15 mol % of diethylene glycol residues, based on 100 mol % of the total molar amount of diol residues in the first copolyester;

[0338] (2) greater than 50% by weight and less than 80% by weight of PET;

[0339] (3) greater than 0 wt % and less than 20 wt % of a compatibilizer;

[0340] The blend has a measurable crystallization temperature Tc or a crystallization enthalpy ΔHc greater than 1 J / g as measured by differential scanning calorimetry at a cooling rate of 10°C / min;

[0341] The content of the sterically hindered monomer diol residue is greater than 15 mol % based on the total molar amount of diol residues in the blend as 100%;

[0342] The haze of the product is below 50%. Preferably, the haze of the product is below 45%, more preferably, the haze of the product is below 40%, more preferably, the haze of the product is below 35%, more preferably, the haze of the product is below 30%, more preferably, the haze of the product is below 25%, more preferably, the haze of the product is below 20%, more preferably, the haze of the product is below 15%.

[0343] Preferably, the compatibilizer is a second copolyester; preferably, the compatibilizer is a second copolyester comprising a sterically hindered monomer; preferably, the second copolyester comprises a dicarboxylic acid component and a diol component;

[0344] The dicarboxylic acid component of the second copolyester comprises:

[0345] a) 90 to 100 mole % of terephthalic acid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the second copolyester;

[0346] b) 0-10 mol % of other aliphatic and / or aromatic diacid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the second copolyester;

[0347] The diol component in the second copolyester comprises:

[0348] a) based on the total molar amount of diol residues in the second copolyester being 100%, 10-50 mol% of diol residues of a sterically hindered monomer, wherein the sterically hindered monomer is a diol;

[0349] b) 50-90 mol % of ethylene glycol residues, based on 100 mol % of the total molar amount of glycol residues in the second copolyester;

[0350] c) 0-15 mol % of diethylene glycol residues, based on 100 mol % of the total molar amount of diol residues in the second copolyester.

[0351] Preferably, the steric hindered monomer in the second copolyester is one or more of neopentyl glycol, 2-methyl-1,3-propanediol, and 1,4-cyclohexanedimethanol.

[0352] The embodiment of the present invention also provides a renewable transparent product, which comprises a blend containing PET and copolyester, wherein the blend comprises:

[0353] (1) 20-50 wt% of a first copolyester, wherein the first copolyester has an undetectable crystallization temperature Tc or a crystallization enthalpy ΔHc of less than 1 J / g as measured by differential scanning calorimetry at a cooling rate of 10° C. / min;

[0354] The first copolyester comprises a dicarboxylic acid component and a diol component;

[0355] The dicarboxylic acid component comprises:

[0356] a) 90-100 mol % of terephthalic acid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the first copolyester;

[0357] b) 0-10 mol % of other aliphatic and / or aromatic diacid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the first copolyester;

[0358] The diol component comprises:

[0359] a) based on the total molar amount of diol residues in the first copolyester being 100%, greater than 50 mol% and less than 100 mol% of sterically hindered diol residues, wherein in the first copolyester, the sterically hindered diol residues include:

[0360] 0-100 mol % neopentyl glycol residues;

[0361] 0-30 mol % of 2-methyl-1,3-propanediol residues;

[0362] 0-50 mol % of 1,4-cyclohexanedimethanol residues;

[0363] b) 0-50 mol % of ethylene glycol residues, based on 100 mol % of the total molar amount of glycol residues in the first copolyester;

[0364] c) 0-15 mol % of diethylene glycol residues, based on 100 mol % of the total molar amount of diol residues in the first copolyester;

[0365] (2) greater than 50% by weight and less than 80% by weight of PET;

[0366] The first copolyester and the PET are mixed and melted by a shear heating mixing device;

[0367] The blend has a measurable crystallization temperature Tc or a crystallization enthalpy ΔHc greater than 1 J / g as measured by differential scanning calorimetry at a heating rate of 10°C / min;

[0368] The content of the sterically hindered monomer diol residue is greater than 15 mol % based on the total molar amount of diol residues in the blend as 100%;

[0369] The haze of the product is below 50%. Preferably, the haze of the product is below 45%, more preferably, the haze of the product is below 40%, more preferably, the haze of the product is below 35%, more preferably, the haze of the product is below 30%, more preferably, the haze of the product is below 25%, more preferably, the haze of the product is below 20%, more preferably, the haze of the product is below 15%.

[0370] The embodiment of the present invention further provides a renewable transparent product, which comprises a blend containing PET and copolyester, wherein the blend is prepared by the following preparation method, which comprises the following steps:

[0371] (1) mixing and melting 20-50 wt % of the first copolyester and more than 50 wt % and less than 80 wt % of PET by a shear heating mixing device to obtain a melt blend;

[0372] The first copolyester has an undetectable crystallization temperature Tc or a crystallization enthalpy ΔHc of less than 1 J / g as measured by differential scanning calorimetry at a cooling rate of 10° C. / min;

[0373] The first copolyester comprises a dicarboxylic acid component and a diol component;

[0374] The dicarboxylic acid component comprises:

[0375] a) 90-100 mol % of terephthalic acid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the first copolyester;

[0376] b) 0-10 mol % of other aliphatic and / or aromatic diacid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the first copolyester;

[0377] The diol component comprises:

[0378] a) based on the total molar amount of diol residues in the first copolyester being 100%, greater than 50 mol% and less than 100 mol% of sterically hindered diol residues, wherein in the first copolyester, the sterically hindered diol residues include:

[0379] 0-100 mol % neopentyl glycol residues;

[0380] 0-30 mol % of 2-methyl-1,3-propanediol residues;

[0381] 0-50 mol % of 1,4-cyclohexanedimethanol residues;

[0382] b) 0-50 mol % of ethylene glycol residues, based on 100 mol % of the total molar amount of glycol residues in the first copolyester;

[0383] c) 0-15 mol % of diethylene glycol residues, based on 100 mol % of the total molar amount of diol residues in the first copolyester;

[0384] (2) cooling the molten blend to form a shape;

[0385] The blend has a measurable crystallization temperature Tc or a crystallization enthalpy ΔHc greater than 1 J / g as measured by differential scanning calorimetry at a heating rate of 10°C / min;

[0386] The content of the sterically hindered monomer diol residue is greater than 15 mol % based on the total molar amount of diol residues in the blend as 100%;

[0387] The haze of the product is below 50%. Preferably, the haze of the product is below 45%, more preferably, the haze of the product is below 40%, more preferably, the haze of the product is below 35%, more preferably, the haze of the product is below 30%, more preferably, the haze of the product is below 25%, more preferably, the haze of the product is below 20%, more preferably, the haze of the product is below 15%.

[0388] Preferably, the shear heating mixing equipment is a twin-screw extruder or a reactor with a stirring device.

[0389] Preferably, in the renewable transparent products of the above embodiments of the present invention, based on the total weight of the blend being 100%, the content of the steric hindrance monomer is greater than 15% by weight.

[0390] Preferably, in the renewable transparent products of the above-mentioned embodiments of the present invention, the steric hindered monomer in the first copolyester includes neopentyl glycol; preferably, based on the total molar amount of glycol residues in the first copolyester as 100%, the content of neopentyl glycol residues is 55-90 mole%, more preferably, based on the total molar amount of glycol residues in the first copolyester as 100%, the content of neopentyl glycol residues is 60-80 mole%, more preferably, based on the total molar amount of glycol residues in the first copolyester as 100%, the content of neopentyl glycol residues is 65-70 mole%.

[0391] Preferably, in the renewable transparent products of the above-mentioned embodiments of the present invention, the steric hindered monomers in the first copolyester include neopentyl glycol and 2-methyl-1,3-propanediol; preferably, based on the total molar amount of the diol residues in the first copolyester as 100%, the content of the neopentyl glycol residues is 40-90 mole%, and the content of the 2-methyl-1,3-propanediol residues is 5-25 mole%; more preferably, based on the total molar amount of the diol residues in the first copolyester as 100%, the content of the neopentyl glycol residues is 45-80 mole%, and the content of the 2-methyl-1,3-propanediol residues is 5-15 mole%; more preferably, based on the total molar amount of the diol residues in the first copolyester as 100%, the content of the neopentyl glycol residues is 50-70 mole%, and the content of the 2-methyl-1,3-propanediol residues is 5-10 mole%.

[0392] Preferably, in the renewable transparent products of the above embodiments of the present invention, the steric hindered monomers in the first copolyester include neopentyl glycol and 1,4-cyclohexanedimethanol; preferably, based on the total molar amount of glycol residues in the first copolyester as 100%, the content of the neopentyl glycol residues is 10-90 mol%, and the content of the 1,4-cyclohexanedimethanol residues is 10-45 mol%; more preferably, based on the total molar amount of glycol residues in the first copolyester as 100%, the content of the neopentyl glycol residues is 20-70 mol%. , the 1,4-cyclohexanedimethanol residue content is 20-40 mol%; more preferably, based on the total molar amount of the glycol residues in the first copolyester as 100%, the neopentyl glycol residue content is 25-60 mol%, and the 1,4-cyclohexanedimethanol residue content is 25-40 mol%; more preferably, based on the total molar amount of the glycol residues in the first copolyester as 100%, the neopentyl glycol residue content is 25-45 mol%, and the 1,4-cyclohexanedimethanol residue content is 20-35 mol%.

[0393] Preferably, in the renewable transparent products of the above embodiments of the present invention, the steric hindered monomers in the first copolyester include neopentyl glycol, 1,4-cyclohexanedimethanol and 2-methyl-1,3-propanediol; preferably, based on the total molar amount of glycol residues in the first copolyester as 100%, the content of the neopentyl glycol residues is 10-90 mol%, the content of the 1,4-cyclohexanedimethanol residues is 10-45 mol%, and the content of the 2-methyl-1,3-propanediol residues is 5-25 mol%; more preferably, based on the total molar amount of glycol residues in the first copolyester as 100%, the content of the neopentyl glycol residues is 10-90 mol%, the content of the 1,4-cyclohexanedimethanol residues is 10-45 mol%, and the content of the 2-methyl-1,3-propanediol residues is 5-25 mol%. More preferably, based on the total molar amount of the glycol residues in the first copolyester as 100%, the content of the neopentyl glycol residues is 20-70 mol%, the content of the 1,4-cyclohexanedimethanol residues is 15-40 mol%, and the content of the 2-methyl-1,3-propanediol residues is 5-15 mol%; more preferably, based on the total molar amount of the glycol residues in the first copolyester as 100%, the content of the neopentyl glycol residues is 25-60 mol%, the content of the 1,4-cyclohexanedimethanol residues is 20-40 mol%, and the content of the 2-methyl-1,3-propanediol residues is 5-10 mol%.

[0394] Preferably, in the above-mentioned renewable transparent product of each embodiment of the present invention, the glass transition temperature Tg of the first copolyester measured by differential scanning calorimetry at a heating rate of 10°C / min is greater than 60°C and less than 100°C.

[0395] Preferably, in the above-mentioned renewable transparent products of various embodiments of the present invention, the intrinsic viscosity of the blend measured in 60 / 40 (wt / wt) phenol / tetrachloroethane at a concentration of 0.5 g / 100 ml at 25° C. is 0.50 to 1.2 dL / g.

[0396] Preferably, in the renewable transparent products of the above-mentioned embodiments of the present invention, the rPET is physical rPET.

[0397] Preferably, in the above-mentioned renewable transparent products of each embodiment of the present invention, the thickness of the product is 0.04-10mm; more preferably, the thickness of the product is 0.08-10mm; more preferably, the thickness of the product is 0.2-10mm; more preferably, the thickness of the product is 0.3-10mm; more preferably, the thickness of the product is 0.4-10mm; more preferably, the thickness of the product is 0.5-10mm; more preferably, the thickness of the product is 1-10mm; more preferably, the thickness of the product is 0.2mm, 0.4mm, 0.6mm, 0.8mm, 1mm, 1.2mm, 1.4mm, 1.8mm, 2mm, 2.4mm, 2.8mm, 3mm, 3.6mm, 4mm, 4.2mm, 4.6mm, 5mm, 6mm, 7mm, 8mm, 9mm, 10mm.

[0398] The products are, for example, packaging products, tool handles, eyeglass frames, toys, electrical parts, various containers, molded products, etc. In particular, the products are thick-walled products. The thick-walled products made from the blends of the embodiments of the present invention contain a high content of PET and have transparent properties, and are recyclable due to their certain crystallinity.

[0399] The blends of the embodiments of the present invention can be used to prepare various types of products by preparation methods known in the art, such as products made by various moldings, extrusions, and blow moldings, including but not limited to thermoformed or thermoformable products, injection molded products, extrusion molded products, injection blow molded products, injection stretch blow molded products, and extrusion blow molded products.

[0400] Obviously, those skilled in the art know that since there is no qualitative difference in composition and properties between virgin PET (i.e., non-recycled PET, which is polymerized from the main components of ethylene glycol and terephthalic acid) and rPET, when the technical effects of carbon reduction and environmental protection are not considered, and only the technical effects of transparency and easy recycling of thick-walled products are considered, the PET in the technical solution of the embodiment of the present invention is not limited to rPET. The PET in the present invention can be: virgin PET, or physical rPET, or chemical rPET, or a mixture of virgin PET and physical rPET, or a mixture of virgin PET and chemical rPET, or a mixture of physical rPET and chemical rPET, or a mixture of virgin PET, physical rPET and chemical rPET. When PET adopts rPET, additional technical effects of carbon reduction and environmental protection can be produced.

[0401] The "copolyester" in the present invention refers to a polyester containing more than one structural repeating unit. Polyester is a conventional polymer in the art, which is produced by the esterification reaction between a divalent or higher valent carboxylic acid and a divalent or higher valent alcohol.

[0402] The "repeating unit" in the present invention refers to an organic structure having a dicarboxylic acid residue and a diol residue bonded via an ester group.

[0403] "Residue" in the present invention refers to any organic structure incorporated into a polymer from a corresponding monomer by polycondensation and / or esterification reactions.

[0404] The "terephthalic acid" in the present invention includes terephthalic acid itself and its residues which can be used in the reaction method for preparing polyester with diols, and any derivatives of terephthalic acid, including its related acid halides, esters, half esters, salts, half salts, acid anhydrides, mixed anhydrides and / or mixtures thereof or their residues, for example, including dimethyl terephthalate.

[0405] The present invention is further explained in detail below by way of preferred embodiments. It should be noted that unless explicitly limited, these embodiments are for illustrative purposes only and are not intended to limit the scope of the present invention. In other words, the present invention is not limited to the following specific implementation methods, and any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

[0406] Preparation of the first copolyester

[0407] Four first copolyesters numbered I-1, I-2, I-3, and I-4 were prepared in the embodiment of the present invention. In addition, three copolyesters as comparative examples were prepared according to the prior art and numbered C-1, C-2, and C-3.

[0408] The preparation method of the first copolyester I-1 is as follows: in a stainless steel autoclave equipped with a stirrer, a thermometer and a reflux condenser, 7000g of terephthalic acid PTA (42.2×100% mol), 784g of ethylene glycol EG (42.2×25%×1.2 mol), 536g of diethylene glycol DEG (42.2×10%×1.2 mol), and 3421g of neopentyl glycol NPG (42.2×65%×1.2 mol) are slurried and added into the reactor. It should be noted that the molar amount of all diol components here is based on 42.2 mol of terephthalic acid (about 7000g), and is obtained by multiplying the molar ratio of the diols in I-1 in Table 1 by 1.2 times, which is a common practice in the field of polyester synthesis. In addition, 100 ppm of tetrabutyl titanate catalyst relative to 7000 g of terephthalic acid, 450 ppm of ethylene glycol antimony catalyst relative to 7000 g of terephthalic acid, 300 ppm of triphenyl phosphite and 300 ppm of anhydrous sodium acetate relative to 7000 g of terephthalic acid are added, mixed with the diol component and the dicarboxylic acid component, and heated to about 260° C. under a nitrogen atmosphere. The pressure in the reactor is maintained at about 0.2 MPa until the esterification rate is about 98%. The pressure in the reactor is adjusted to normal pressure, the temperature is raised to about 280° C., and the pressure is gradually reduced to about 50 Pa. The polycondensation is carried out under reduced pressure for about 3 hours to synthesize the first copolyester I-1 of the embodiment, whose intrinsic viscosity is 0.76 dL / g.

[0409] The preparation steps of the first copolyesters I-2, I-3, I-4 and comparative examples C-1, C-2, C-3 are similar to the preparation method of the first copolyester I-1. The molar amounts of the diol components are all synthesized based on 42.2 mol of terephthalic acid and the diol molar ratios in Table 1.

[0410] Table 1 Composition and crystallinity of the first copolyester

[0411]

[0412] The meaning of the content of each component in the first copolyester in Table 1 is the same as the definition of the content of dicarboxylic acid residues and diol residues in the first copolyester described above, wherein "MPO+CHDM+NPG mol%" refers to the molar percentage of the sum of the molar amounts of MPO+CHDM+NPG diol residues in the total molar amount of the diol components in the first copolyester. PTA is terephthalic acid with a molecular weight of 166, IPA is isophthalic acid with a molecular weight of 166, EG is ethylene glycol with a molecular weight of 62, DEG is diethylene glycol with a molecular weight of 106, MPO is 2-methyl-1,3-propanediol with a molecular weight of 90, CHDM is 1,4-cyclohexanedimethanol with a molecular weight of 144, and NPG is neopentyl glycol with a molecular weight of 104.

[0413] Preparation of 4 mm thick sheets

[0414] Sheets were prepared using the method for preparing the blend described in the embodiments of the present invention, and the sheets were numbered AX or AX-10. In addition, comparative example sheets were prepared according to the prior art, and were numbered CA-X or CA-X-10.

[0415] The preparation method of sheet A-1 is as follows: the first copolyester I-1 and physical method rPET (Guangxi Guolong GL018082, intrinsic viscosity IV = 0.82 dL / g) are blended in a mass ratio of 3:7 and added to a twin-screw extruder, and extruded into granules at 260°C. Then the granules are added to the screw of the injection molding machine, and then melted at 250-270°C and injected into a mold of 4mm*80mm*50mm (thickness*length*width), with an injection time of 2 seconds, a holding time of 2 seconds, and a cooling time of 25 seconds.

[0416] The preparation methods of other sheets and comparative examples CA-1, CA-2, CA-3, CA-4, CA-5, and CA-6 are the same as that of sheet A-1, except that their components and contents are changed, among which 10 weight percent of compatibilizer C-1 is added to A-6, A-1-10, and A-5-10, as shown in Table 2.

[0417] The preparation method of comparative example CA-7 is as follows: the first copolyester I-1 and the physical method rPET (Guangxi Guolong GL018082, IV = 0.82dL / g) are physically blended at a mass ratio of 3:7, and the physically blended particles are directly added to a single screw extruder, melted at 250-270°C, and then injected into a 4mm*80mm*50mm (thickness*length*width) mold, with an injection time of 2 seconds, a holding time of 2 seconds, and a cooling time of 25 seconds. Unlike Example A-1, CA-7 does not use a twin-screw extruder for mixed extrusion granulation, does not use a shear heating mixing step, and does not use a compatibilizer, as shown in Table 2.

[0418] Comparative Example CA-8 is a commercially available copolyester product WS-501 produced by Jiangyin Huahong. The copolyester product contains 28 mol% of steric monomer neopentyl glycol (NPG) diol residues, based on the total molar amount of diol residues as 100%. It is made by copolymerizing terephthalic acid with two diols, ethylene glycol and NPG. Its preparation method is different from the blending preparation method of the embodiment of the present invention. The product is completely transparent, but has no crystallinity, and is therefore difficult to regenerate and recover.

[0419] In Table 2, "rPET" refers to physical rPET; "hindered monomer content" refers to the sum of the diol residue contents of NPG+CHDM+MPO, based on the total molar amount of diol residues in the blend as 100 mol%, obtained by nuclear magnetic resonance detection.

[0420] In Table 2, transmittance and haze are used to characterize the optical properties of the sheet. If the material has strong crystallinity during the preparation process, the core of the sheet will crystallize and turn white due to failure to cool in time. In addition, when the two phases are incompatible, the sheet will also become turbid and white. The above crystallization and / or incompatibility of the two phases will cause the haze of the sheet to be greater than 50%, and the sheet will be opaque. For sheets without obvious core crystallization and with good compatibility between the two phases, the haze is below 50%, and the sheet is transparent.

[0421] In Table 2, the transmittance difference and haze difference are used to characterize the changes in transmittance and haze of the blend or its product due to crystallization and / or compatibility. mi The light transmittance T of the first copolyester co The transmittance difference is T mi -T co , blend haze H mi The haze H of the first copolyester co The haze difference is H mi -H co , the difference in light transmittance and haze between the two is small, which means that after mixing more than 50 weight% of rPET, the optical performance decreases less. Since the first copolyester is a transparent non-crystalline copolyester, the decrease in optical performance after mixing rPET to form a blend is mainly caused by rPET. When the above-mentioned light transmittance difference and haze difference are small, for example, less than 10%, it means that the blend or its thick-walled product made from it has not formed white core caused by crystallization, and there is no obvious incompatibility between the two phases, and the blend or its product is transparent; on the contrary, once white core caused by crystallization and / or incompatibility between the two phases occurs, the light transmittance difference and haze difference are large, for example, greater than 20%, and the blend or its product is opaque.

[0422] It should be noted that, combining the two parameters of haze and haze difference, it can be seen that the haze value of the sheet in the embodiment of the present invention is affected by the haze value of the first copolyester. The first copolyester is a transparent non-crystalline copolyester. Under normal production process, its haze value is usually below 10%. The first copolyester of the batch in this embodiment is affected by accidental process factors, and its haze value is slightly higher, but it is still transparent. Those skilled in the art can understand that under normal production process, the haze value of the blend in the embodiment of the present invention will be lower than 20% or even lower, and the transparency effect of the product will be better.

[0423] In Table 2, from the perspective of transmittance and haze performance, in Examples A-1, A-1-10, A-2, A-3, A-4, A-5, and A-5-10, when the first copolyesters I-1, I-2, and I-3 are respectively mixed with 50-70 wt% of physical rPET bottle flakes, the transmittance difference T of the prepared 4 mm thick sheet is mi -T co All less than 10%, haze difference H mi -H co Less than 10%, the sheet is transparent; in comparative examples CA-4, CA-5, and CA-6, the copolyesters C-1, C-2, and C-3 of the comparative examples are mixed with 50-70 weight % of the physical method rPET bottle flakes to prepare a 4 mm thick sheet with a light transmittance difference of T mi -T co Greater than 30%, haze difference H mi -H co Greater than 40%, the sheet is opaque. The reason why the comparative examples CA-5 and CA-6 sheets are opaque is that the molar content of the steric hindrance monomer in the blend is too low, only 6% and 7% respectively, which leads to crystallization of the blend. Therefore, the content of the steric hindrance monomer in the blend is one of the important factors for whether the blend is transparent. According to the experimental data of each embodiment and comparative example, it can be known that when the total molar amount of diol residues in the blend is 100%, the content of the diol residues of the steric hindrance monomer is greater than 15 mol% (see the "Content of Steric Hindered Monomer" column in Table 2), a transparent blend can be obtained. More preferably, the content of the steric hindrance monomer is greater than 15 weight % based on the total weight of the blend as 100%. The reasons for the opacity of A-6 and CA-4 will be discussed below.

[0424] In Table 2, from the perspective of transmittance and haze performance, Example A-1-10 containing 10 wt% of compatibilizer, when containing 60 wt% of physical rPET bottle flakes, the sheet is transparent, and its transmittance difference T mi -T co 2%, haze difference H mi -H coThe transmittance difference of the opaque comparative example CA-4 is 35% and the haze difference is 40%, which is significantly lower than that of the opaque comparative example CA-4, indicating that the use of a compatibilizer can solve the opacity problem caused by a high rPET content.

[0425] In Table 2, from the perspective of transmittance and haze performance, when the content of steric hindrance monomer in Example A-1-10 is lower than that in Example A-2, the transmittance difference and haze difference of Example A-1-10 using a compatibilizer are 5% lower and 6% lower than the corresponding transmittance difference and haze difference of Example A-2 without a compatibilizer. This shows that the addition of a compatibilizer while adopting a shear heating mixing process can further reduce the haze of the blend and improve the transparency of the blend. It also shows that the preparation process of blending the first copolyester and rPET in the form of a compatibilizer as a separate component can obtain better transparency than the process without a compatibilizer.

[0426] In Table 2, from the perspective of transmittance and haze performance, although Example A-6 contains 10 wt % of compatibilizer, its transmittance is worse than T mi -T co Up to 60%, haze difference H mi -H co The haze H is 67%, the sheet is opaque, and the sheet is not transparent. In Example A-5, when 70 wt% of physical rPET is mixed and no compatibilizer is used, the transmittance difference T mi -T co Only 6%, haze difference H mi -H co It is only 7%, and the sheet is transparent, which indicates that when the content of 1,4-cyclohexanedimethanol (CHDM) in the first copolyester is too high, the sheet will be opaque after mixing with physical rPET. The experimental results of comparative example CA-4 also show that when the CHDM content is too high, the sheet will be opaque. Therefore, when the steric hindered monomer in the first copolyester includes 1,4-cyclohexanedimethanol (CHDM), the total molar amount of glycol residues in the first copolyester is 100%, and the content of 1,4-cyclohexanedimethanol residues is below 50 mol% to avoid opacity of the sheet.

[0427] In Table 2, from the perspective of transmittance and haze performance, the transmittance difference T of Example A-1, which does not contain a compatibilizer but is subjected to shear mixing and heating in a twin-screw extruder and melt extrusion granulation, is mi -T co 6%, haze difference H mi -H co The light transmittance of the sheet formed by direct injection molding was 5%. The comparative example CA-7 with the same formula did not use twin-screw extrusion melt granulation, did not adopt the shear heating mixing step, and did not use a compatibilizer. mi -T co Up to 64%, haze difference Hmi -H co Up to 70%, the edges and the interior of the sheet are opaque. This shows that shear heating mixing plays a key role in improving the optical properties of the blends and can solve the opacity problem.

[0428] In Table 2, on the basis of maintaining good transmittance and haze, the crystallinity and melting temperature of the blend are further examined. Products made of a blend with certain crystallinity and a melting temperature greater than 220°C will not stick together due to increased temperature when being recycled and are easy to recycle.

[0429] In Table 2, the haze difference T of Examples A-1, A-2, A-3, A-4, A-5, A-1-10, and A-5-10 mi -T co Less than 10%, and DSC can measure the crystallization temperature; while the haze difference T of comparative examples CA-1, CA-2, and CA-3 mi -T co Although it is less than 10%, the crystallization temperature cannot be measured and the material is in an amorphous state. It is easy to cause adhesion when heated during the recycling process, which is not conducive to recycling and has poor recyclability.

[0430] In Table 2, the melting temperatures of Examples A-1, A-2, A-3, A-4, A-5, A-1-10, and A-5-10 are all above 230°C. Those skilled in the art know that when the melting temperature of the blend is below 220°C, it will be lower than the heating temperature of the general bottle flake physical recycling procedure, so that it is easy to melt and bond in the recycling procedure, resulting in recycling difficulties. However, the blends of the embodiments of the present invention will not melt due to heating during the recycling process when recycled, so they are easy to recycle.

[0431] In Table 2, the comparative examples CA-4 and CA-8 and the embodiments A-2 and A-4 have similar contents of steric monomers, but different preparation methods. CA-8 is a copolyester prepared by copolymerization of terephthalic acid and two diols, ethylene glycol and CHDM, while CA-4, A-2 and A-4 are prepared by blending the first copolyester and rPET. However, their crystallinity shows great differences. The crystallization temperature of CA-8 cannot be measured, and the material is amorphous, while the other three blends all show crystallinity. It can be seen that the preparation method can play a key role in the crystallinity of the sample. The materials with similar contents of steric monomers prepared by the blending process in the embodiments of the present invention are completely different in crystallinity compared with the CA-8 copolyester in the prior art.

[0432] In summary, since the first copolyester is a non-crystalline copolyester and is transparent, when it forms a blend with the crystalline rPET, the transmittance will decrease and the haze will increase due to crystallization and / or poor compatibility. When the transmittance decreases too much and the haze increases too much, the resulting blend will be opaque. The present invention solves the technical problem of opacity caused by crystallization and / or poor compatibility by optimizing the formula and process.

[0433] T g 、T cc 、T m 、T c The detection methods of heat of crystallization are as follows:

[0434] The method of measuring the copolyester (10 mg) or blend sample (10 mg) prepared in the above examples by differential scanning calorimetry DSC is as follows: First, in the first cycle, the temperature is increased from 30°C to 280°C at a rate of 10°C / min to eliminate the thermal history, and then decreased to 20°C at a rate of 10°C / min to test the thermal crystallization peak temperature T of the sample. c , calculated at Tc as the integral of the crystallization enthalpy ΔH c The second cycle was then heated from 20°C to 280°C at a rate of 10°C / min, and the heat absorption and heat release of the sample were measured. During the heating process, the first heat absorption temperature was the glass transition temperature (T g ), T g The exothermic temperature measured afterwards is the cold crystallization temperature (T cc ), in T cc The integral is the heat of crystallization ΔH cc If the sample undergoes thermal crystallization during the first cycle of cooling, T cc The peak is not obvious or even disappears. In the present invention, the crystallization peak temperature and crystallization enthalpy mentioned, unless otherwise specified, refer to the thermal crystallization temperature T measured during the first cycle of cooling. c and ΔH c The greater the value of the crystallization heat, the faster the crystallization rate and the greater the rate of transformation to the crystalline phase. cc The endothermic temperature measured later is the melting point (T m ). m The integral is calculated as the melting enthalpy ΔH m .

[0435]

Claims

1. A blend containing PET and copolyester, characterized in that: The blend comprises: (1) 20-50 wt% of a first copolyester, wherein the first copolyester has an undetectable crystallization temperature Tc or a crystallization enthalpy ΔHc of less than 1 J / g as measured by differential scanning calorimetry at a cooling rate of 10° C. / min; The first copolyester comprises a dicarboxylic acid component and a diol component; The dicarboxylic acid component comprises: a) 90-100 mol % of terephthalic acid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the first copolyester; b) 0-10 mol % of other aliphatic and / or aromatic diacid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the first copolyester; The diol component comprises: a) based on the total molar amount of diol residues in the first copolyester being 100%, greater than 50 mol% and less than 100 mol% of sterically hindered diol residues, wherein in the first copolyester, the sterically hindered diol residues include: 0-100 mol % neopentyl glycol residues; 0-30 mol % of 2-methyl-1,3-propanediol residues; 0-50 mol % of 1,4-cyclohexanedimethanol residues; b) 0-50 mol % of ethylene glycol residues, based on 100 mol % of the total molar amount of glycol residues in the first copolyester; c) 0-15 mol % of diethylene glycol residues, based on 100 mol % of the total molar amount of diol residues in the first copolyester; (2) greater than 50% by weight and less than 80% by weight of PET; (3) greater than 0 wt % and less than 20 wt % of a compatibilizer; preferably, the compatibilizer is a second copolyester; preferably, the compatibilizer is a second copolyester containing a sterically hindered monomer; The blend has a measurable crystallization temperature Tc or a crystallization enthalpy ΔHc greater than 1 J / g as measured by differential scanning calorimetry at a cooling rate of 10°C / min; When the blend is used to prepare a sheet with a thickness of 4 mm by an injection molding process, the haze of the sheet is less than 50%; Based on the total molar amount of diol residues in the blend as 100%, the content of the diol residues of the sterically hindered monomer is greater than 15 mol%.

2. The blend according to claim 1, characterized in that The second copolyester comprises a dicarboxylic acid component and a diol component; The dicarboxylic acid component of the second copolyester comprises: a) 90 to 100 mole % of terephthalic acid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the second copolyester; b) 0-10 mol % of other aliphatic and / or aromatic diacid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the second copolyester; The diol component in the second copolyester comprises: a) based on the total molar amount of diol residues in the second copolyester being 100%, 10-50 mol% of diol residues of a sterically hindered monomer, wherein the sterically hindered monomer is a diol; b) 50-90 mol % of ethylene glycol residues, based on 100 mol % of the total molar amount of glycol residues in the second copolyester; c) 0-15 mol % of diethylene glycol residues, based on 100 mol % of the total molar amount of diol residues in the second copolyester.

3. The blend according to claim 2, characterized in that The steric hindered monomer in the second copolyester is one or more of neopentyl glycol, 2-methyl-1,3-propanediol, and 1,4-cyclohexanedimethanol.

4. A blend containing PET and copolyester, characterized in that: The blend comprises: (1) 20-50 wt% of a first copolyester, wherein the first copolyester has an undetectable crystallization temperature Tc or a crystallization enthalpy ΔHc of less than 1 J / g as measured by differential scanning calorimetry at a cooling rate of 10° C. / min; The first copolyester comprises a dicarboxylic acid component and a diol component; The dicarboxylic acid component comprises: a) 90-100 mol % of terephthalic acid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the first copolyester; b) 0-10 mol % of other aliphatic and / or aromatic diacid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the first copolyester; The diol component comprises: a) based on the total molar amount of diol residues in the first copolyester being 100%, greater than 50 mol% and less than 100 mol% of sterically hindered diol residues, wherein in the first copolyester, the sterically hindered diol residues include: 0-100 mol % neopentyl glycol residues; 0-30 mol % of 2-methyl-1,3-propanediol residues; 0-50 mol % of 1,4-cyclohexanedimethanol residues; b) 0-50 mol % of ethylene glycol residues, based on 100 mol % of the total molar amount of glycol residues in the first copolyester; c) 0-15 mol % of diethylene glycol residues, based on 100 mol % of the total molar amount of diol residues in the first copolyester; (2) greater than 50% by weight and less than 80% by weight of PET; The first copolyester and the PET are mixed and melted by a shear heating mixing device; The blend has a measurable crystallization temperature Tc or a crystallization enthalpy ΔHc greater than 1 J / g as measured by differential scanning calorimetry at a heating rate of 10°C / min; When the blend is used to prepare a sheet with a thickness of 4 mm by an injection molding process, the haze of the sheet is less than 50%; Based on the total molar amount of diol residues in the blend as 100%, the content of the diol residues of the sterically hindered monomer is greater than 15 mol%.

5. The blend according to claim 1 or 4, characterized in that Based on the total weight of the blend being 100%, the content of the steric hindered monomer is greater than 15 weight %.

6. The blend according to claim 1 or 4, characterized in that The steric hindered monomer in the first copolyester includes neopentyl glycol; preferably, based on the total molar amount of glycol residues in the first copolyester as 100%, the content of the neopentyl glycol residues is 55-90 mol%, more preferably, based on the total molar amount of glycol residues in the first copolyester as 100%, the content of the neopentyl glycol residues is 60-80 mol%, more preferably, based on the total molar amount of glycol residues in the first copolyester as 100%, the content of the neopentyl glycol residues is 65-70 mol%; or, The steric hindered monomer in the first copolyester includes neopentyl glycol and 2-methyl-1,3-propanediol; preferably, based on the total molar amount of glycol residues in the first copolyester as 100%, the content of neopentyl glycol residues is 40-90 mol%, and the content of 2-methyl-1,3-propanediol residues is 5-25 mol%; more preferably, based on the total molar amount of glycol residues in the first copolyester as 100%, the content of neopentyl glycol residues is 45-80 mol%, and the content of 2-methyl-1,3-propanediol residues is 5-15 mol%; more preferably, based on the total molar amount of glycol residues in the first copolyester as 100%, the content of neopentyl glycol residues is 50-70 mol%, and the content of 2-methyl-1,3-propanediol residues is 5-10 mol%; or, The steric hindered monomers in the first copolyester include neopentyl glycol and 1,4-cyclohexanedimethanol; preferably, based on the total molar amount of glycol residues in the first copolyester as 100%, the content of the neopentyl glycol residues is 10-90 mol%, and the content of the 1,4-cyclohexanedimethanol residues is 10-45 mol%; more preferably, based on the total molar amount of glycol residues in the first copolyester as 100%, the content of the neopentyl glycol residues is 20-70 mol%, and the content of the 1,4-cyclohexanedimethanol residues is 20-70 mol%. The residue content is 20-40 mol%; more preferably, based on the total molar amount of glycol residues in the first copolyester as 100%, the neopentyl glycol residue content is 25-60 mol%, and the 1,4-cyclohexanedimethanol residue content is 25-40 mol%; more preferably, based on the total molar amount of glycol residues in the first copolyester as 100%, the neopentyl glycol residue content is 25-45 mol%, and the 1,4-cyclohexanedimethanol residue content is 20-35 mol%; or, The steric hindered monomers in the first copolyester include neopentyl glycol, 1,4-cyclohexanedimethanol and 2-methyl-1,3-propanediol; preferably, based on the total molar amount of glycol residues in the first copolyester as 100%, the content of the neopentyl glycol residues is 10-90 mol%, the content of the 1,4-cyclohexanedimethanol residues is 10-45 mol%, and the content of the 2-methyl-1,3-propanediol residues is 5-25 mol%; more preferably, based on the total molar amount of glycol residues in the first copolyester as 100%, the content of the The content of the neopentyl glycol residues is 20-70 mol%, the content of the 1,4-cyclohexanedimethanol residues is 15-40 mol%, and the content of the 2-methyl-1,3-propanediol residues is 5-15 mol%; more preferably, based on the total molar amount of the glycol residues in the first copolyester as 100%, the content of the neopentyl glycol residues is 25-60 mol%, the content of the 1,4-cyclohexanedimethanol residues is 20-40 mol%, and the content of the 2-methyl-1,3-propanediol residues is 5-10 mol%.

7. A method for preparing a blend containing PET and copolyester, characterized in that: The following steps are involved: (1) mixing and melting 20-50 wt % of the first copolyester and more than 50 wt % and less than 80 wt % of PET by a shear heating mixing device to obtain a melt blend; The first copolyester has an undetectable crystallization temperature Tc or a crystallization enthalpy ΔHc of less than 1 J / g as measured by differential scanning calorimetry at a cooling rate of 10° C. / min; The first copolyester comprises a dicarboxylic acid component and a diol component; The dicarboxylic acid component comprises: a) 90-100 mol % of terephthalic acid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the first copolyester; b) 0-10 mol % of other aliphatic and / or aromatic diacid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the first copolyester; The diol component comprises: a) based on the total molar amount of diol residues in the first copolyester being 100%, greater than 50 mol% and less than 100 mol% of sterically hindered diol residues, wherein in the first copolyester, the sterically hindered diol residues include: 0-100 mol % neopentyl glycol residues; 0-30 mol % of 2-methyl-1,3-propanediol residues; 0-50 mol % of 1,4-cyclohexanedimethanol residues; b) 0-50 mol % of ethylene glycol residues, based on 100 mol % of the total molar amount of glycol residues in the first copolyester; c) 0-15 mol % of diethylene glycol residues, based on 100 mol % of the total molar amount of diol residues in the first copolyester; (2) cooling the molten blend to form a shape; The blend has a measurable crystallization temperature Tc or a crystallization enthalpy ΔHc greater than 1 J / g as measured by differential scanning calorimetry at a heating rate of 10°C / min; When the blend is used to prepare a sheet with a thickness of 4 mm by an injection molding process, the haze of the sheet is less than 50%; Based on the total molar amount of diol residues in the blend as 100%, the content of the diol residues of the sterically hindered monomer is greater than 15 mol%. Preferably, the shear heating mixing equipment is a twin-screw extruder or a reactor with a stirring device.

8. A renewable transparent product, characterized in that: The product comprises the blend according to any one of claims 1 to 6, or comprises the blend prepared by the preparation method according to claim 7.

9. A renewable transparent product, characterized in that: It comprises a blend comprising PET and a copolyester, the blend comprising: (1) 20-50 wt% of a first copolyester, wherein the first copolyester has an undetectable crystallization temperature Tc or a crystallization enthalpy ΔHc of less than 1 J / g as measured by differential scanning calorimetry at a cooling rate of 10° C. / min; The first copolyester comprises a dicarboxylic acid component and a diol component; The dicarboxylic acid component comprises: a) 90-100 mol % of terephthalic acid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the first copolyester; b) 0-10 mol % of other aliphatic and / or aromatic diacid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the first copolyester; The diol component comprises: a) based on the total molar amount of diol residues in the first copolyester being 100%, greater than 50 mol% and less than 100 mol% of sterically hindered diol residues, wherein in the first copolyester, the sterically hindered diol residues include: 0-100 mol % neopentyl glycol residues; 0-30 mol % of 2-methyl-1,3-propanediol residues; 0-50 mol % of 1,4-cyclohexanedimethanol residues; b) 0-50 mol % of ethylene glycol residues, based on 100 mol % of the total molar amount of glycol residues in the first copolyester; c) 0-15 mol % of diethylene glycol residues, based on 100 mol % of the total molar amount of diol residues in the first copolyester; (2) greater than 50% by weight and less than 80% by weight of PET; (3) greater than 0 wt % and less than 20 wt % of a compatibilizer; preferably, the compatibilizer is a second copolyester; preferably, the compatibilizer is a second copolyester containing a sterically hindered monomer; The blend has a measurable crystallization temperature Tc or a crystallization enthalpy ΔHc greater than 1 J / g as measured by differential scanning calorimetry at a cooling rate of 10°C / min; The content of the sterically hindered monomer diol residue is greater than 15 mol % based on the total molar amount of diol residues in the blend as 100%; The haze of the product is below 50%.

10. A renewable transparent product, characterized in that: It comprises a blend containing PET and copolyester, wherein the blend is prepared by the following preparation method, which comprises the following steps: (1) mixing and melting 20-50 wt % of the first copolyester and more than 50 wt % and less than 80 wt % of PET by a shear heating mixing device to obtain a melt blend; The first copolyester has an undetectable crystallization temperature Tc or a crystallization enthalpy ΔHc of less than 1 J / g as measured by differential scanning calorimetry at a cooling rate of 10° C. / min; The first copolyester comprises a dicarboxylic acid component and a diol component; The dicarboxylic acid component comprises: a) 90-100 mol % of terephthalic acid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the first copolyester; b) 0-10 mol % of other aliphatic and / or aromatic diacid residues, based on 100 mol % of the total molar amount of dicarboxylic acid residues in the first copolyester; The diol component comprises: a) based on the total molar amount of diol residues in the first copolyester being 100%, greater than 50 mol% and less than 100 mol% of sterically hindered diol residues, wherein in the first copolyester, the sterically hindered diol residues include: 0-100 mol % neopentyl glycol residues; 0-30 mol % of 2-methyl-1,3-propanediol residues; 0-50 mol % of 1,4-cyclohexanedimethanol residues; b) 0-50 mol % of ethylene glycol residues, based on 100 mol % of the total molar amount of glycol residues in the first copolyester; c) 0-15 mol % of diethylene glycol residues, based on 100 mol % of the total molar amount of diol residues in the first copolyester; (2) cooling the molten blend to form a shape; The blend has a measurable crystallization temperature Tc or a crystallization enthalpy ΔHc greater than 1 J / g as measured by differential scanning calorimetry at a heating rate of 10°C / min; The content of the sterically hindered monomer diol residue is greater than 15 mol % based on the total molar amount of diol residues in the blend as 100%; The haze of the product is below 50%. Preferably, the shear heating mixing equipment is a twin-screw extruder or a reactor with a stirring device.